Coextruded, crosslinked multi-layer polyolefin foam structure from recycled polyolefin material and method of manufacturing the same
Patent Information
- Application Number
- JP2024187436
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2014-12-30
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-26
Smart Images

Figure 2025026848000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Patent Application No. 14 / 586,721, filed December 30, 2014, U.S. Patent Application No. 14 / 586,745, filed December 30, 2014, and U.S. Patent Application No. 14 / 586,781, filed December 30, 2014, the contents of which are incorporated herein by reference in their entireties.
[0002] FIELD OF THEINVENTION The present invention relates to a multi-layer polyolefin foam structure, more particularly to a coextruded crosslinked polyolefin multi-layer foam structure. [Background technology]
[0003] Over the past 30 years, manufacturing industries have successfully recycled many types of waste: newspapers, cardboard, aluminum, steel, glass, various plastics, films, foams, etc. In the case of plastics, there are certain types of plastic waste that are not easily recycled into commercially viable new products. One such type of waste is metallized polyolefin materials.
[0004] Metallized polyolefins are often used as barrier films in the food packaging industry. For example, metallized polyolefin films are used in potato chip bags, snack bar wrappers, etc. Other applications of metallized polyolefin films, particularly polypropylene films, include packaging for electronic and medical devices and dielectrics in electronic film capacitors.
[0005] Another application of metallized polyolefins, especially polypropylene, is in the plating industry. Decorative chrome plating (trivalent chromium) of injection molded polypropylene is common on parts of home appliances and other durable and non-durable consumer goods. Also common is the decorative vacuum metallization of polypropylene and polyethylene molded parts and thermoformed sheeting, including, for example, confectionery trays.
[0006] Metal plating of polypropylene parts is also not limited to decorative applications: engineering requirements such as EMI and RFI shielding, static dissipation, abrasion resistance, heat resistance, and thermal and chemical barriers may require metal plating of polypropylene parts.
[0007] Currently, various methods and systems exist for the recovery and recycling of various films and foams, including films and foams that contain metallized polyolefins. Furthermore, as manufacturers continue to attempt to adopt "greener" techniques in their manufacturing processes, the demand for commercial use of these recycled materials is increasing. However, whenever recycled materials are used in manufacturing processes, various problems arise. Summary of the Invention
[0008] Applicants have found that the use of recycled materials to create foam structures can result in undesirable foam surface variations. These undesirable surface variations include, among others, undesirable surface roughness, undesirable surface softness, undesirable surface hardness, surface energy, and undesirable surface adhesion. In certain commercial applications, such as in the automotive interiors industry, foam surface properties are important. When used in automotive interiors, laminators typically laminate films, fabrics, fiber layers, or leather to the foam. The foam laminate can then typically be thermoformed onto a rigid polypropylene, ABS, or wood fiber composite substrate. To successfully form a foam laminate and / or to form a foam laminate by thermoforming, it is necessary to eliminate foam surface variations. Surface variations on the foam surface can adversely affect lamination strength and quality.
[0009] An example of an undesirable surface characteristic is shown in Figures 5A and 5B. The foam in Figures 5A and 5B contains 8% parts per 100 parts resin ("PPHR") of shredded (not cryogenically ground) factory scrap crosslinked polypropylene / polyethylene blend foam. As shown in Figures 5A and 5B, the black recycled foam that was not completely crushed, dispersed, and otherwise reincorporated into these foam sheets can be seen as dark spots and "gels". These spots and "gels" can cause problems in adhering films, fabrics, fiber layers, or leathers to these foams by a laminator. In particular, the "gels" can become less adhesive and peel off during secondary operations such as thermoforming, causing visible blister-like defects on the film, fabric, fiber layer, or leather.
[0010] Applicants have discovered co-extruded multi-layer foam structures that include a surface foam layer(s) derived from virgin (non-recycled) polyolefin materials and an inner foam layer(s) derived from one or more recycled polyolefin materials. Additionally, these foam structures can include a recycled foam layer(s) sandwiched or embedded between two non-recycled foam layers. Thus, these multi-layer foam structures allow manufacturers to use recycled materials in succession to create lower cost, more environmentally friendly products that can meet the same specifications as foam structures made entirely from non-recycled materials.
[0011] Described are multi-layer foam structures and methods of making and using these structures. More specifically, described are formulations of physically crosslinked, co-continuous extruded multi-layer foam structures with closed cell morphology. These formulations can utilize recycled polyolefin materials and incorporate them into layers. As described herein, "structures" include, but are not limited to, layers, films, webs, sheets, or other similar structures.
[0012] Some embodiments include a method of forming a multi-layer structure by co-extruding a foam layer and a film layer on a side of the foam layer. The foam layer can include polypropylene and / or polyethylene and a chemical blowing agent. The foam layer can also include a crosslinking agent, and the chemical blowing agent can be azodicarbonamide. The film layer can include polypropylene and / or polyethylene. The polypropylene of both layers can have a melt flow index of 0.1 to 25 grams per 10 minutes at 230°C. The polyethylene of both layers can have a melt flow index of 0.1 to 25 grams per 10 minutes at 190°C.
[0013] In some embodiments, these coextrusion structures can be irradiated with ionizing radiation. The coextrusion structures can be irradiated up to four times. The ionizing radiation can be alpha rays, beta rays, gamma rays, or an electron beam. Additionally, the ionizing radiation can be an electron beam having an acceleration voltage of 200 to 1500 kV. The radiation dose of the electron beam can be 10 to 500 kGy. The ionizing radiation can crosslink the coextrusion structure to a crosslinking degree of 20 to 75%.
[0014] In some embodiments, irradiated coextruded structures may be foamed as well. The foaming process can be continuous to form a foam structure. Foaming may include heating the structure using molten salts, radiant heaters, vertical hot air ovens, horizontal hot air ovens, microwave energy, or combinations thereof.
[0015] Multi-layer foam structure: 20~250kg / m 3 and a thickness of 0.2 to 50 mm. Further, the foam layer may have an average closed cell size of 0.05 to 1.0 mm and an average surface roughness of less than 80 μm.
[0016] Some embodiments include a method of forming a multi-layer structure by co-extruding a first foam layer and a second foam layer on the side of the first foam layer. The first foam layer can include polypropylene and / or polyethylene and a first chemical blowing agent. The second foam layer can include polypropylene and / or polyethylene and a second chemical blowing agent. The polypropylene of both layers can have a melt flow index of 0.1 to 25 grams per 10 minutes at 230°C. The polyethylene of both layers can have a melt flow index of 0.1 to 25 grams per 10 minutes at 190°C. The first and / or second foam layers can also include a crosslinking agent. Additionally, the first and / or second chemical blowing agent can be azodicarbonamide.
[0017] In some embodiments, these coextrusion structures can be irradiated with ionizing radiation. The coextrusion structures can be irradiated up to four times. The ionizing radiation can be alpha rays, beta rays, gamma rays, or an electron beam. Additionally, the ionizing radiation can be an electron beam having an acceleration voltage of 200 to 1500 kV. The radiation dose of the electron beam can be 10 to 500 kGy. The ionizing radiation can crosslink the coextrusion structure to a crosslinking degree of 20 to 75%.
[0018] In some embodiments, irradiated coextruded structures may be foamed as well. The foaming process can be continuous to form a foam structure. Foaming may include heating the structure using molten salts, radiant heaters, vertical hot air ovens, horizontal hot air ovens, microwave energy, or combinations thereof.
[0019] Multi-layer foam structure: 20~250kg / m 3 and a thickness of 0.2-50 mm. Further, the multi-layer foam structure may have an average closed cell size of 0.05-1.0 mm. Further, the first foam layer and / or the second foam layer may have an average surface roughness of less than 80 μm.
[0020] Some embodiments include a method of forming a multi-layer structure by co-extruding a first layer and a second layer on the side of the first layer. The first layer can include polypropylene and / or polyethylene and a first chemical blowing agent. The second layer can include 5-75% by weight recycled metallized polyolefin material, 25-95% by weight polypropylene, polyethylene, or a blend of polypropylene and polyethylene, and a second chemical blowing agent. Additionally, a third layer can be co-extruded on the side of the second layer opposite the first layer. The third layer can include polypropylene and / or polyethylene and a third chemical blowing agent. Additionally, the first and / or third layers can be substantially free of recycled polyolefin material. Additionally, any or all of the first, second, or third layers can include a crosslinking agent. Additionally, any or all of the first, second, or third chemical blowing agents can be azodicarbonamide. The polypropylene in either layer may have a melt flow index of 0.1 to 25 grams per 10 minutes at 230° C. The polyethylene in either layer may have a melt flow index of 0.1 to 25 grams per 10 minutes at 190° C.
[0021] The recycled metallized polyolefin material can be small enough to pass through a 0.95 cm (0.375 inch) standard sieve. Additionally, the recycled metallized polyolefin material may have a metal layer or layers with a total thickness of 0.003 to 100 μm prior to being recycled.
[0022] In some embodiments, these coextrusion structures can be irradiated with ionizing radiation. The coextrusion structures can be irradiated up to four times. The ionizing radiation can be alpha rays, beta rays, gamma rays, or an electron beam. Additionally, the ionizing radiation can be an electron beam having an acceleration voltage of 200 to 1500 kV. The radiation dose of the electron beam can be 10 to 500 kGy. The ionizing radiation can crosslink the coextrusion structure to a crosslinking degree of 20 to 75%.
[0023] In some embodiments, irradiated coextruded structures may be foamed as well. The foaming process can be continuous to form a foam structure. Foaming may include heating the structure using molten salts, radiant heaters, vertical hot air ovens, horizontal hot air ovens, microwave energy, or combinations thereof.
[0024] Multi-layer foam structure: 20~250kg / m 3 and a thickness of 0.2-50 mm. Further, the multi-layer foam structure may have an average closed cell size of 0.05-1.0 mm. Further, the first foam layer and / or the third foam layer may have an average surface roughness of less than 80 μm.
[0025] Some embodiments include a multi-layer foam structure having a co-extruded first foam layer comprising polypropylene and / or polyethylene and a second foam layer on the side of the co-extruded first foam layer. The second foam layer can comprise 5-75% by weight recycled metallized polyolefin material and 25-95% by weight polypropylene, polyethylene, or a blend of polypropylene and polyethylene. The multi-layer foam structure can also include a third co-extruded foam layer on the side of the second foam layer opposite the first foam layer. The third layer can comprise polypropylene and / or polyethylene. The first foam layer and / or the third foam layer can be substantially free of recycled polyolefin material. The polypropylene of either layer can have a melt flow index of 0.1-25 grams per 10 minutes at 230°C. The polyethylene of either layer can have a melt flow index of 0.1-25 grams per 10 minutes at 190°C.
[0026] Multi-layer foam structure: 20~250kg / m 3and a thickness of 0.2-50 mm. Further, the multilayer foam structure may have an average closed cell size of 0.05-1.0 mm. The multilayer foam structure may also have a degree of crosslinking of 20-75%. Further, the first foam layer and / or the third foam layer may have an average surface roughness of less than 80 μm. Further, in some embodiments, the multilayer foam structure may be slit, friction sawed, sheared, heat cut, laser cut, plasma cut, water jet cut, die cut, mechanically cut, or manually cut to form products.
[0027] Some embodiments include a laminate including a multi-layer foam structure and a laminate layer. The multi-layer foam structure can include a co-extruded first foam layer including polypropylene and / or polyethylene and a second co-extruded foam layer on a side of the first foam layer. The second foam layer can include 5-75% by weight recycled metallized polyolefin material and 25-95% by weight polypropylene, polyethylene, or a blend of polypropylene and polyethylene. The laminate layer can be on a side of the first foam layer opposite the second foam layer. The laminate layer can be a film, fabric, fiber layer, or leather. The first foam layer can have an average surface roughness of less than 80 μm. The multi-layer foam structure can also include a third co-extruded foam layer on a side of the second foam layer opposite the first foam layer. The third layer can include polypropylene and / or polyethylene. The first and / or third layers can be substantially free of recycled polyolefin material. Additionally, the laminate can be further thermoformed onto the substrate on the side of the third foam layer opposite the second foam layer.
[0028] Some embodiments include a method of forming a multi-layer structure by co-extruding a first layer and a second layer on the side of the first layer. The first layer can include polypropylene and / or polyethylene and a first chemical blowing agent. The second layer can include 5-50% by weight recycled crosslinked polyolefin foam material, 50-95% by weight polypropylene, polyethylene, or a blend of polypropylene and polyethylene, and a second chemical blowing agent. Additionally, a third layer can be co-extruded on the side of the second layer, opposite the first layer. The third layer can include polypropylene and / or polyethylene and a third chemical blowing agent. Additionally, the first and / or third layers can be substantially free of recycled polyolefin material. Additionally, any or all of the first, second, or third layers can include a crosslinking agent. Additionally, any or all of the first, second, or third chemical blowing agents can be azodicarbonamide. The polypropylene in either layer may have a melt flow index of 0.1 to 25 grams per 10 minutes at 230° C. The polyethylene in either layer may have a melt flow index of 0.1 to 25 grams per 10 minutes at 190° C.
[0029] The recycled crosslinked polyolefin foam material can be cryogenically ground polyolefin foam material that is small enough to pass through a 3.5 U.S. standard mesh.
[0030] In some embodiments, these coextrusion structures can be irradiated with ionizing radiation. The coextrusion structures can be irradiated up to four times. The ionizing radiation can be alpha rays, beta rays, gamma rays, or an electron beam. Additionally, the ionizing radiation can be an electron beam having an acceleration voltage of 200 to 1500 kV. The radiation dose of the electron beam can be 10 to 500 kGy. The ionizing radiation can crosslink the coextrusion structure to a crosslinking degree of 20 to 75%.
[0031] In some embodiments, irradiated coextruded structures may be foamed as well. The foaming process can be continuous to form a foam structure. Foaming may include heating the structure using molten salts, radiant heaters, vertical hot air ovens, horizontal hot air ovens, microwave energy, or combinations thereof.
[0032] Multi-layer foam structure: 20~250kg / m 3 and a thickness of 0.2-50 mm. Further, the multi-layer foam structure may have an average closed cell size of 0.05-1.0 mm. Further, the first foam layer and / or the third foam layer may have an average surface roughness of less than 80 μm.
[0033] Some embodiments include a multi-layer foam structure having a co-extruded first foam layer comprising polypropylene and / or polyethylene and a second foam layer on the side of the co-extruded first foam layer. The second foam layer can comprise 5-50% by weight recycled crosslinked polyolefin foam material and 50-95% by weight polypropylene, polyethylene, or a blend of polypropylene and polyethylene. The multi-layer foam structure can also include a third co-extruded foam layer on the side of the second foam layer opposite the first foam layer. The third layer can comprise polypropylene and / or polyethylene. The first foam layer and / or the third foam layer can be substantially free of recycled polyolefin material. The polypropylene of any layer can have a melt flow index of 0.1-25 grams per 10 minutes at 230°C. The polyethylene of any layer can have a melt flow index of 0.1-25 grams per 10 minutes at 190°C. The recycled crosslinked polyolefin foam material can include cryogenically ground polyolefin foam material.
[0034] Multi-layer foam structure: 20~250kg / m 3and a thickness of 0.2-50 mm. Further, the multilayer foam structure may have an average closed cell size of 0.05-1.0 mm. The multilayer foam structure may also have a degree of crosslinking of 20-75%. Further, the first foam layer and / or the third foam layer may have an average surface roughness of less than 80 μm. Further, in some embodiments, the multilayer foam structure may be slit, friction sawed, sheared, heat cut, laser cut, plasma cut, water jet cut, die cut, mechanically cut, or manually cut to form products.
[0035] Some embodiments include a laminate including a multi-layer foam structure and a laminate layer. The multi-layer foam structure can include a first co-extruded foam layer including polypropylene and / or polyethylene and a second co-extruded foam layer on a side of the first foam layer. The second foam layer can include 5-50% by weight recycled crosslinked polyolefin foam material and 50-95% by weight polypropylene, polyethylene, or a blend of polypropylene and polyethylene. The laminate layer can be on a side of the first foam layer opposite the second foam layer. The laminate layer can be a film, fabric, fiber layer, or leather. The first foam layer can have an average surface roughness of less than 80 μm. The recycled crosslinked polyolefin foam material can include cryogenically ground polyolefin foam material. The multi-layer foam structure can also include a third co-extruded foam layer on a side of the second foam layer opposite the first foam layer. The third layer can include polypropylene and / or polyethylene. The first and / or third layers can be substantially free of recycled polyolefin material, and the laminate can be further thermoformed onto the substrate on the side of the third foam layer opposite the second foam layer.
[0036] It will be understood that aspects and embodiments of the invention described herein include "consisting of" and / or "consisting essentially of" aspects and embodiments. For all methods, systems, compositions, and devices described herein, the methods, systems, compositions, and devices can include the recited elements or steps, or can "consist of" or "consist essentially of" the recited elements or steps. When a system, composition, or device is described as "consisting essentially of," the recited elements, system, composition, or device includes the recited elements and may include other elements that do not substantially affect the performance of the system, composition, or device, but does not include any other elements that substantially affect the performance of the system, composition, or device other than those elements expressly recited, or does not include additional elements in sufficient concentrations or amounts to substantially affect the performance of the system, composition, or device. When a method is described as "consisting essentially of" the recited steps, the method includes the recited steps and may include other steps that do not substantially affect the outcome of the method, but the method does not include any other steps that substantially affect the outcome of the method other than those steps expressly recited.
[0037] In the present disclosure, in various embodiments, "substantially free of" a particular element, composition, compound, or ingredient means that less than about 5%, less than about 2%, less than about 1%, less than about 0.5%, less than about 0.1%, less than about 0.05%, less than about 0.025%, or less than about 0.01% by weight of the particular element, composition, compound, or ingredient is present. Preferably, "substantially free of" a particular element, composition, compound, or ingredient indicates that less than about 1% by weight of the particular element, composition, compound, or ingredient is present.
[0038] Additional advantages of the present invention will become readily apparent to those skilled in the art from the following detailed description. As will be seen from the following description, the present invention is capable of other and different embodiments, and its details are capable of modification in various obvious respects, all of which can be made without departing from the present invention. Thus, the examples and descriptions should be regarded as illustrative in nature, rather than restrictive. Exemplary embodiments of the present invention will now be described with reference to the accompanying drawings. [Brief description of the drawings]
[0039] [Figure 1A] 1 is a backlit magnified photograph of the foam of Example 1. [Figure 1B] 1 is a frontlit, non-magnified photograph of the foam of Example 1. [Figure 1C] 1 is a backlight enlarged photograph of Example 1 in the case of non-foaming. [Figure 2A] 1 is a backlit magnified photograph of the foam of Example 2. [Figure 2B] 1 is a frontlit, non-magnified photograph of the foam of Example 2. [Figure 2C] 1 is a backlight enlarged photograph of Example 2 in the case of non-foaming. [Figure 3A] 1 is a first backlit close-up photograph of the foam of Example 3. [Figure 3B] 1 is a second backlit close-up photograph of the foam of Example 3. [Figure 3C] 1 is a first frontlit non-magnified photograph of the foam of Example 3. [Figure 3D] 1 is a second frontlit non-magnified photograph of the foam of Example 3. [Figure 3E] 1 is a backlight enlarged photograph of Example 3 in the case of non-foaming. [Figure 4A] 1 is a backlit magnified photograph of the foam of Example 4. [Figure 4B] 1 is a frontlit, non-magnified photograph of the foam of Example 4. [Figure 4C] 1 is a backlight enlarged photograph of Example 4 in the case of non-foaming. [Figure 5A] 1 is a first photograph of a foam comprising shredded recycled crosslinked polyolefin foam. [Figure 5B] 2 is a second photograph of a foam comprising shredded recycled crosslinked polyolefin foam. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0040]
[0056] Described is a method for making a coextruded crosslinked closed cell multilayer foam structure. A layer or layers of the multilayer foam structure can be derived from recycled polyolefin material. The method for making the coextruded crosslinked closed cell multilayer foam structure including a recycled polyolefin foam layer can include the steps of (a) coextrusion, (b) irradiation, and (c) foaming.
[0041]
[0057] Coextrusion is the simultaneous extrusion of multiple layers of material. This type of extrusion uses two or more extruders to deliver a constant volumetric throughput of material to an extrusion head (die) that can extrude the material into the desired shape.
[0042] (0058) In the co-extrusion step, the foam composition can be fed to multiple extruders to form the non-foamed multi-layer structure. For example, the "A" foam composition can be fed to one extruder and the "B" foam composition can be fed to a second extruder. The method of feeding the components to the extruders can be based on the design of the available extruders and material handling equipment. If necessary, pre-blending of the components of the foam composition can be performed to facilitate their dispersion. A Henschel mixer can be used for such pre-blending. All components can be pre-blended and fed through a single port of the extruder. The components can also be fed through separate ports that are individually designed for each component. For example, if the crosslinking accelerator or any other additives are liquid, the accelerator and / or additives can be added through the feed gate(s) of the extruder or through the vent openings of the extruder (if vents are provided) instead of pre-blending with the solid components. A combination of "pre-blending" and port feeding of the individual components can also be used.
[0043]
[0059] Each extruder can feed a steady amount of each composition into one or more manifolds followed by a sheet extrusion die to produce a non-foamed coextruded multilayer sheet. There are two common methods for coextruding the materials: (1) a feedblock manifold, and (2) multiple manifolds in a die. Components of a feedblock manifold can include (a) inlet ports for the top, middle and bottom layers, (b) a laminar melt lamination area that directs the separate flow streams into one stratified melt stream in the feedblock, (c) an adapter plate between the feedblock and a sheet die, and / or (d) a sheet die (similar to a monolayer die) where the stratified melt streams enter the center of the die and spread out along the manifolds as separate multilayer extrudates flowing out the die exit. The components of a multi-manifold die can be similar to a single layer die, except that (a) there are two or more feed channels, (b) each melt channel has its own choker bar for flow control, and / or (c) the melt streams converge within the die near the exit and emerge as separate multi-layer extrudates.
[0044]
[0060] The layer thickness can be determined by the design of the manifold (single or multiple) and die. For example, an 80 / 20 feedblock manifold can deliver compositions in about a 4:1 ratio if the speed and size of each extruder are matched accordingly. This ratio can vary depending on, for example, (a) the relative extrusion speed between one extruder and another, (b) the relative size of each extruder, and / or (c) the composition (i.e., viscosity) of the individual layers.
[0045]
[0061] The overall multilayer sheet thickness can be controlled by the overall die gap. However, the overall multilayer sheet thickness can be further adjusted, for example, by drawing (i.e., "stretching") the molten multilayer extrudate and / or smoothing the molten multilayer extrudate through a nip.
[0046] (0062) The multi-layer structure can include at least two layers composed of different compositions. In some embodiments, the multi-layer structure includes at least two layers composed of different foam compositions. In some embodiments, the multi-layer structure includes at least one non-recycled polyolefin layer and at least one recycled polyolefin layer. For example, the structure can be an A / B layer structure, an A / B / A layer structure, an A / B / C layer structure, or can have multiple other layers. In some structures, the B layer can include recycled polyolefin material and the A layer can include non-recycled polyolefin material. However, both A, B, and other layers can be composed of non-recycled polyolefin material or recycled polyolefin material as well. Furthermore, the multi-layer structure can include additional layers, such as tie layers, film layers, and / or additional foam layers (including additional recycled and / or non-recycled layers), among others.
[0047]
[0063] The foam composition fed to the extruder to form the non-recycled layer(s) can include at least one polypropylene, at least one polyethylene, or a combination thereof. The polypropylene(s) and / or polyethylene(s) can include the same types described below for recycled metallized polyolefin materials. That is, polypropylene includes, but is not limited to, polypropylene, impact modified polypropylene, polypropylene-ethylene copolymer, impact modified polypropylene-ethylene copolymer, metallocene polypropylene, metallocene polypropylene-ethylene copolymer, metallocene polypropylene olefin block copolymer (with controlled block sequence), polypropylene-based polyolefin plastomer, polypropylene-based polyolefin elastoplastomer, polypropylene-based polyolefin elastomer, polypropylene-based thermoplastic polyolefin blend, and polypropylene-based thermoplastic elastomer blend. Additionally, the polypropylene can be grafted with maleic anhydride. Further, the polyethylenes include, but are not limited to, LDPE, LLDPE, VLDPE, VLLDPE, HDPE, polyethylene-propylene copolymers, metallocene polyethylene, metallocene ethylene-propylene copolymers, and metallocene polyethylene olefin block copolymers (with controlled block sequences), any of which may include grafted compatibilizers or copolymers containing acetate and / or ester groups. These polyethylenes may be grafted with maleic anhydride. These polyethylenes may also be copolymers and terpolymers containing acetate and / or ester groups, or ionomers containing acetate and / or ester groups. The foam composition fed to the extruder to form the non-recycled layer(s) may include at least about 75% by weight, preferably at least about 90% by weight, more preferably at least about 95% by weight, and even more preferably at least about 98% by weight of non-recycled polypropylene, polyethylene, or combinations thereof.Additionally, the foam composition fed to the extruder to form the non-recycled layer(s) can be substantially free of recycled polyolefin material. The foam composition fed to the extruder to form the non-recycled layer(s) can also be 100% by weight virgin or non-recycled material.
[0048]
[0064] Because the disclosed foam compositions can be used to make a wide variety of multi-layer foam products and laminates, a wide variety of polypropylenes and polyethylenes can be used in the foam compositions to meet various end-use requirements of structures, products, and laminates.
[0049]
[0065] The foam composition fed to the extruder to form the recycled layer(s) can include recycled materials, including but not limited to recycled polyolefin materials, recycled metallized polyolefin materials, recycled polyolefin film materials, recycled polyolefin metallized film materials, recycled polyolefin foam materials, recycled polyolefin metallized foam materials, or combinations thereof. The foam composition fed to the extruder to form the recycled layer(s) can include at least about 5% by weight, preferably at least about 10% by weight, more preferably at least about 15% by weight of recycled materials. Additionally, these foam compositions fed to the extruder to form the recycled layer(s) can include at least about 25% by weight, preferably at least about 30% by weight, more preferably at least about 40% by weight of polypropylene, polyethylene, or combinations thereof.
[0050]
[0066] When the foam fed to the extruder to form the recycled layer(s) includes recycled metallized polyolefin material, the foam composition can include from about 5 to about 75 weight percent, preferably from about 10 to about 70 weight percent, and more preferably from about 20 to about 60 weight percent recycled metallized polyolefin material. Additionally, these recycled metallized polyolefin foam compositions can include from about 25 to about 95 weight percent, preferably from about 30 to about 90 weight percent, and more preferably from about 40 to about 80 weight percent polypropylene, polyethylene, or a combination thereof.
[0051]
[0067] Recycled metallized polyolefin material can be obtained in various forms. Examples include, but are not limited to, pellets, granules, chips, flakes, beads, cylinders, rods, lint, and powder. In some embodiments, recycled metallized polyolefin material can be obtained as uniform pellets using the process disclosed in WO2013057737A2, which is incorporated herein by reference in its entirety. In some embodiments, chips or flakes of recycled metallized polyolefin material can be obtained from plastic crushers and shredders that are commonly used to reduce the size of waste profiles, injection molded pieces, and the like. In a third example, ground metallized polyolefin material can be obtained from commercial pulverizing equipment or cryogenic grinding.
[0052]
[0068] Regardless of the form, recycled pieces will preferably be reduced in size to pass through a standard 0.375 inch sieve. Recycled pieces that do not pass through a standard 0.375 inch sieve may have difficulty being adequately sheared and mixed with other components in the extruder. This may result in a less than uniform structure.
[0053]
[0069] The primary source of metallized polyolefins is the metallization and metal coating industries. These industries obtain metallized polyolefins using various techniques including vacuum metallization, arc or flame spraying, electroless plating, or electroless plating followed by electroplating. Coatings are often not limited to one metal layer. Polyolefins coated with various metal multi-layers deposited using different techniques can also be used in the disclosed invention.
[0054]
[0070] Metallized polyolefins can be obtained by vacuum metallization, arc or flame spraying, electroless plating, or electroless plating followed by electroplating. Each technique for obtaining metallized polyolefins is briefly described below.
[0055]
[0071] In vacuum metallization, metal is evaporated in a vacuum chamber. The vapor then condenses on the substrate surface, leaving a thin layer of metal coating. This deposition process is also commonly called physical vapor deposition (PVD).
[0056]
[0072] In flame spraying, a handheld device is used to spray a metallic coating layer onto a substrate. The primary force driving the deposition is a combustion flame driven by oxygen and gas. Metallic powder is heated and melted. The combustion flame accelerates the mixture and expels it as a spray.
[0057] (0073) Arc spraying is similar to flame spraying, but the energy source is different. Instead of relying on a burning flame, arc spraying gets its energy from an electric arc. Two wires made of a metallic coating material carrying a DC current are contacted together at their tips. When the two wires come into contact, the energy released heats and melts the wires, while a gas stream deposits the molten metal onto the substrate surface, producing a metal layer.
[0058] (0074) In chemical plating, the surface of the plastic is etched away using an oxidizer solution. As a result of the oxidizer solution the surface becomes highly susceptible to hydrogen bonding, which is usually increased during the application of a coating. When the polyolefin material (after etching) is immersed in a solution containing metal ions, a coating occurs that bonds to the plastic surface as a metal layer.
[0059]
[0075] For electroplating (electrolytic plating) to be successful, the polyolefin surface must first be made conductive, which can be accomplished by chemical plating. Once the polyolefin surface is conductive, the substrate is immersed in the solution. In the solution, a metal salt is connected to a positive source of electrical current (cathode). An anodic (negatively charged) conductor is also placed in the bath, which completes an electrical circuit with the positively charged salt. The metal salt is electrically attracted to the substrate, where a metal layer is produced. As this process occurs, the anodic conductor, usually made from the same type of metal as the metal salt, dissolves into the solution and replaces the source of metal salt, which is depleted during deposition.
[0060]
[0076] The amount of coating that can be deposited by each technique varies. Depending on the end-use requirements, one technique may be preferred over another. Nevertheless, the metal coatings deposited by these techniques will range from about 0.003 μm for a single layer to 100 μm for a multi-layer coating, preferably 0.006 μm for a single layer to 75 μm for a multi-layer coating, and more preferably 0.01 μm for a single layer to 50 μm for a multi-layer coating. The metal in the recycled metallized polyolefin varies from about 0.05 to about 5% by weight.
[0061] (0077) The most common metal coating applied to polyolefins is aluminum. Less common coatings are trivalent chromium, nickel and copper. Further less common coatings are codeposited metals such as, but not limited to, tin, hexavalent chromium, gold, silver and nickel-chromium. Those skilled in the art will understand that these metal coatings are not necessarily pure elemental coatings. For example, "nickel" may be nickel-phosphorus or nickel-boron alloys, and "copper" may be copper-zinc alloys (brass) or copper-tin alloys (bronze). Whether the metal is alloyed or not, the particular metal is still the major coating component. It will be preferred that the metal coating comprises 70-100% of the indicated metal, more preferably 80-100% of the indicated metal, and even more preferably 85-100% of the indicated metal. Those skilled in the art will understand that the surface of the metal layer can be oxidized and some metals can be tarnished.
[0062]
[0078] Both polypropylene and polyethylene films can be vacuum metallized in the film metallization industry. It should therefore be expected that any recycled metallized polyolefin may contain at least one polypropylene or at least one polyethylene, or a mixture of both. For barrier applications (as opposed to decorative applications), both polypropylene and polyethylene films may be coextruded with other barrier layers such as EVOH and PVOH. In such cases, these multi-layer films may have adhesive "tie layers" to bond the EVOH and PVOH to the polypropylene or polyethylene. These tie layers range in polyolefins from OBC to polyethylene with acetate or ester groups to polyethylene ionomers.
[0063]
[0079] Similarly, maleic anhydride grafted polypropylene and polyethylene are also used in industry to improve adhesion, bonding not only to EVOH or PVOH, but also to metal coatings.
[0064]
[0080] In the metal coating industry, polypropylene is often preferred over polyethylene. However, due to the broader end-use requirements of the products produced in this industry, polypropylene may be blended with other olefins to meet, for example, softness requirements, impact requirements, or tack requirements. Thus, any recycled metallized polyolefins from this industry may be blended with polyolefins.
[0065]
[0081] The polypropylene(s) containing polyolefin component of recycled polyolefin may contain an elastic or softening component, typically ethylene, an α-olefin, or a rubber component. Thus, in this disclosure, the term "polypropylene" includes, but is not limited to, polypropylene, impact modified polypropylene, polypropylene-ethylene copolymer, impact modified polypropylene-ethylene copolymer, metallocene polypropylene, metallocene polypropylene-ethylene copolymer, metallocene polypropylene olefin block copolymer (with controlled block sequence), polypropylene based polyolefin plastomer, polypropylene based polyolefin elastoplastomer, polypropylene based polyolefin elastomer, polypropylene based thermoplastic polyolefin blend, and polypropylene based thermoplastic elastomer blend.
[0066]
[0082] A non-limiting example of "polypropylene" is isotactic homopolypropylene. Commercially available examples include, but are not limited to, FF018F from Braskem, 3271 from Total Petrochemicals, and COPYLENE® CH020 from Conoco.
[0067]
[0083] A non-limiting example of an "impact modified polypropylene" is an ethylene-propylene (EP) copolymer rubber-containing homopolypropylene. The rubber can be amorphous or semi-crystalline, but is not present in sufficient amounts to impart plastomeric or elastomeric properties to the material. Some non-limiting examples of commercially available "impact modified polypropylene" are Braskem's TI4015F and TI4015F2 and LyondellBasell's Pro-fax® 8623 and Pro-fax® SB786.
[0068]
[0084] "Polypropylene-ethylene copolymer" is polypropylene with random ethylene units. Some non-limiting examples of commercially available "polypropylene-ethylene copolymer" are 6232, 7250FL, and Z9421 from Total Petrochemicals and TR3020F from Braskem.
[0069]
[0085] "Impact modified polypropylene-ethylene copolymer" is a polypropylene with random ethylene units and with an ethylene-propylene (EP) copolymer rubber. The rubber can be amorphous or semi-crystalline, but is not present in sufficient amounts to impart plastomeric or elastoplastomeric properties to the material. A non-limiting example of a commercially available impact modified polypropylene-ethylene copolymer is PRISMA™ 6910 from Braskem.
[0070]
[0086] "Metallocene polypropylene" refers to metallocene syndiotactic homopolypropylene, metallocene atactic homopolypropylene, and metallocene isotactic homopolypropylene. Non-limiting examples of "metallocene polypropylene" are those commercially available under the trade names METOCENE™ from LyondellBasell and ACHIEVE™ from ExxonMobil. Metallocene polypropylene is also commercially available from Total Petrochemicals, including, but not limited to, grades M3551, M3282MZ, M7672, 1251, 1471, 1571, and 1751.
[0071]
[0087] "Metallocene polypropylene-ethylene copolymer" refers to metallocene syndiotactic, metallocene atactic, and metallocene isotactic polypropylenes with random ethylene units. Commercially available examples include, but are not limited to, Lumicene® MR10MX0 and Lumicene® MR60MC2 from Total Petrochemicals and Purell® SM170G from LyondellBasell.
[0072]
[0088] A "metallocene polypropylene olefin block copolymer" is a polypropylene having alternating crystalline hard "blocks" and amorphous soft "blocks" that are not randomly distributed - i.e., in a controlled block sequence. Examples of "metallocene polypropylene olefin block copolymers" include, but are not limited to, the INTUNE™ product line from Dow Chemical Company.
[0073]
[0089] "Polypropylene-based polyolefin plastomers" (POPs) and "polypropylene-based polyolefin elastoplastomers" are both metallocene and non-metallocene propylene-based copolymers having plastomeric and elastoplastomeric properties. Non-limiting examples are commercially available under the trade names VERSIFY™ (metallocene) from Dow Chemical Company, VISTAMAXX™ (metallocene) from ExxonMobil, and KOATTRO™ (non-metallocene) from LyondellBasell (a butene-1 based series of plastomeric polymers - certain grades are butene-1 homopolymer based, others are polypropylene-butene-1 copolymer based materials).
[0074] (0090) "Polypropylene-based polyolefin elastomers" (POE) are both metallocene and non-metallocene propylene-based copolymers with elastomeric properties. Non-limiting examples of propylene-based polyolefin elastomers are polymers available under the trade names THERMORUN™ and ZELAS™ (non-metallocene) from Mitsubishi Chemical Corporation, ADFLEX™ and SOFTELL™ (both non-metallocene) from LyondellBasell, VERSIFY™ (metallocene) from Dow Chemical Company, and VISTAMAXX™ (metallocene) from ExxonMobil.
[0075] (0091) "Polypropylene-based thermoplastic polyolefin blends" (TPOs) are polypropylenes, polypropylene-ethylene copolymers, metallocene homopolypropylenes, and metallocene polypropylene-ethylene copolymers that contain a sufficiently large amount of ethylene-propylene copolymer rubber to impart plastomeric, elastoplastic, or elastomeric properties to the thermoplastic polyolefin blends (TPOs). Non-limiting examples of polypropylene-based polyolefin blends are commercially available polymer blends under the trade names EXCELINK™ from JSR Corporation, THERMORUN™ and ZELAS™ from Mitsubishi Chemical Corporation, FERROFLEX™ and RxLOY™ from Ferro Corporation, and TELCAR™ from Teknor Apex Company.
[0076] (0092) "Polypropylene-based thermoplastic elastomer blends" (TPEs) are polypropylenes, polypropylene-ethylene copolymers, metallocene homopolypropylenes, and metallocene polypropylene-ethylene copolymers with a diblock or multiblock thermoplastic rubber modifier (such as SEBS, SEPS, SEEPS, SEP, SERC, CEBC, HSB, etc.) in a sufficiently large amount to impart plastomeric, elastoplastic, or elastomeric properties to the thermoplastic elastomer blends (TPEs). Non-limiting examples of polypropylene-based thermoplastic elastomer blend polymers are commercially available under the trade names DYNAFLEX® and VERSAFLEX® from GLS Corporation, MONPRENE® and TEKRON® from Teknor Apex Company, and DURAGRIP® from Advanced Polymers Alloys (a division of Ferro Corporation).
[0077]
[0093] All of the above polypropylenes may be grafted with maleic anhydride. Non-limiting examples are ADMER® QF500A and ADMER® QF551A from Mitsui Chemicals. It should be noted that most commercially available anhydride grafted polypropylenes also contain rubber.
[0078]
[0094] The term "polyethylene" includes, but is not limited to, LDPE, LLDPE, VLDPE, VLLDPE, HDPE, polyethylene-propylene copolymers, metallocene polyethylene, metallocene ethylene-propylene copolymers, and metallocene polyethylene olefin block copolymers (with controlled block sequence).
[0079]
[0095] "Metallocene polyethylene" is a metallocene-based polyethylene having properties ranging from non-elastic to elastomeric. Non-limiting examples of metallocene polyethylene are commercially available under the trade names ENGAGE™ from Dow Chemical Company, ENABLE™ and EXCEED™ from ExxonMobil, and EXACT™ from Borealis.
[0080]
[0096] "VLDPE" and "VLLDPE" are very low density polyethylene and linear very low density polyethylene that contain an elastic or softening component, usually an α-olefin. Non-limiting examples of VLDPE and VLLDPE are commercially available under the trade names FLEXOMER™ from Dow Chemical Company and specialty grades STAMYLEX™ from Borealis.
[0081]
[0097] "Metallocene polyethylene olefin block copolymers" are polyethylenes having alternating crystalline hard "blocks" and amorphous soft "blocks" that are not randomly distributed - i.e., in a controlled block sequence. Examples of "metallocene polyethylene olefin block copolymers" include, but are not limited to, the INFUSE™ line of products from Dow Chemical Company.
[0082]
[0098] All of the above polyethylenes may be grafted with maleic anhydride. Non-limiting commercial examples are ADMER® NF539A from Mitsui Chemicals, BYNEL® 4104 from DuPont, and OREVAC® 18360 from Arkema. It should be noted that most commercially available anhydride grafted polyethylenes also contain rubber.
[0083]
[0099] These polyethylenes may also be copolymers and terpolymers containing acetate and / or ester groups. Comonomer groups include, but are not limited to, vinyl acetate, methyl acrylate, ethyl acrylate, butyl acrylate, glycidyl methacrylate, and acrylic acid. Non-limiting examples are commercially available under the trade names BYNEL®, ELVAX®, and ELVALOY® from DuPont; EVATANE®, LOTADER®, and LOTRYL® from Arkema; and ESCORENE™, ESCOR™, and OPTEMA™ from ExxonMobil.
[0084] (0100) These polyethylenes may also be copolymers and terpolymers ionomers containing acetate and / or ester groups. A commonly used comonomer group is, but is not limited to, methacrylic acid. Non-limiting examples are commercially available under the trade names SURLYN® from DuPont; IOTEK™ from ExxonMobil, and AMPLIFY™ IO from Dow Chemical Company.
[0085] (0101) The recycled polyolefin polymer component may also include EVOH and / or PVOH ("PVA"). "EVOH" is a copolymer of ethylene and vinyl alcohol. Non-limiting examples are commercially available under the trade names EVAL™ and EXCEVAL™ from Kuraray, and SOARNOL™ from Nippon Gohsei. "PVOH" is polyvinyl alcohol. Non-limiting examples are commercially available under the trade names ELVANOL® from DuPont, and POVAL®, MOWIOL®, and MOWIFLEX® from Kuraray.
[0086] (0102) Recycled polyolefin foam materials used to form the recycled layer(s) include, but are not limited to, cryogenically ground mill scrap, polypropylene foam, polyethylene foam, or crosslinked foam including polypropylene / polyethylene blend foam. When the foam composition fed to the extruder to form the recycled layer(s) includes recycled polyolefin foam material, the foam composition can include about 5 to about 50% by weight, preferably about 10 to about 45% by weight, and more preferably about 15 to about 40% by weight of recycled polyolefin foam material. Additionally, these recycled polyolefin foam material foam compositions can include about 50 to about 95% by weight, preferably about 55 to about 90% by weight, and more preferably about 60 to about 85% by weight of polypropylene, polyethylene, or a combination thereof.
[0087] (0103) Cryogenic grinding (also known as cryogenic grinding) is a method that can be used to reduce heat-sensitive, oxidizable, and / or "hard to grind" materials to fine powders. Crosslinked polyolefin foam is an example of one such material that does not fit well into readily available grinding systems. In the cryogenic grinding process, a cryogenic liquid such as nitrogen or carbon dioxide can be used to cool the material prior to and / or during grinding to help prevent it from melting and / or to embrittle it. Cryogenically ground mill scrap crosslinked foams (including polypropylene foam, polyethylene foam, and polypropylene / polyethylene blend foams) are commercially available in a variety of particle sizes and particle size distributions from commercial grinders.
[0088]
[0104] Crushing mills are typically equipped with a screen near the discharge chute to ensure that the crushed material is reduced to at least the maximum desired particle size. The crushing screen can be at least 3.5 U.S. standard mesh, preferably at least 6 U.S. standard mesh, and more preferably at least 30 U.S. standard mesh. It may be preferred that the recycled foam material pieces are crushed to a size that passes at least 3.5 U.S. standard mesh (5.6 mm openings), preferably at least 6 U.S. standard mesh (3.35 mm openings), and more preferably at least 30 U.S. standard mesh (0.600 mm openings).
[0089]
[0105] Non-limiting examples of finely ground mill scrap crosslinked polypropylene, polyethylene, and polypropylene / polyethylene blend foams are those manufactured by Midwest Elastomers, Inc. (Wapakoneta, Ohio). Such recycled foam from Midwest Elastomers can be ground using a 30 U.S. standard mesh screen placed near the discharge chute.
[0090] (0106) Recycled polyolefin foam materials can also include foam materials that already contain recycled polyolefin materials. Thus, recycled polyolefin foam materials can include recycled polyolefin materials. For example, recycled polyolefin foam materials may already contain recycled content of metallized polyolefin materials and / or cryogenically ground factor scrap crosslinked foam. Additionally, recycled polyolefin foam materials can include foams derived from recycled metallized polyolefin materials as described in U.S. Patent Application No. 14 / 144,986, which is hereby incorporated by reference in its entirety.
[0091]
[0107] The compositions fed to the extruder to form the various foam layers can include at least one polypropylene having a melt flow index of about 0.1 to about 25 grams per 10 minutes at 230° C. and / or at least one polyethylene having a melt flow index of about 0.1 to about 25 grams per 10 minutes at 190° C. In some embodiments, the melt flow index of the polypropylene(s) and / or polyethylene(s) can be about 0.3 to about 20 grams per 10 minutes at 230° C. and 190° C., respectively, and more preferably about 0.5 to about 15 grams per 10 minutes at 230° C. and 190° C., respectively.
[0092]
[0108] The "Melt Flow Index" (MFI) value of a polymer can be defined and measured according to ASTM D1238 at 230°C for polypropylene and polypropylene-based materials, and at 190°C for polyethylene and polyethylene-based materials, using a 2.16 kg plunger for 10 minutes. For higher melt flow resins, the test time may be reduced.
[0093] (0109) MFI gives a measure of the flow properties of a polymer and is an indicator of the molecular weight and processability of a polymeric material. If the MFI value is too high, it corresponds to a low viscosity, and extrusion according to the present disclosure may not be performed satisfactorily. Problems associated with too high MFI values include low pressure during extrusion, problems in setting the thickness profile, non-uniform cooling profile due to low melt viscosity, insufficient melt strength, equipment problems, or a combination thereof. Problems associated with too low MFI values include high pressure during melt processing, sheet quality and profile problems, and higher extrusion temperatures that risk blowing agent decomposition and activation.
[0094] (0110) The MFI regions are also important for the foaming process because they reflect the viscosity of the material, which in turn influences foaming. Without being bound by any theory, it is believed that there are several reasons why certain MFI values are more effective than others. The longer the molecular chain length, the lower the MFI material may improve some physical properties, creating more energy required for the chains to flow when stress is applied. Also, the longer the molecular chain (MW), the more crystalline entities the chains can crystallize into, thereby providing more strength through intermolecular bonds. However, at too low an MFI, the viscosity becomes too high. On the other hand, polymers with higher MFI values have shorter chains. Thus, in a given volume of higher MFI material, there are more chain ends at the microscopic level, which have the voids required for rotation, and therefore can rotate and create free volume (e.g., the T of the polymer). g (i.e., rotation that occurs above the glass transition temperature). This increase in free volume allows for easy flow under stress.
[0095] (0111) These polypropylene(s) and / or polyethylene(s) of particular MFI values that can be used to form any layer of the foam multilayer structure include the same types as previously described. That is, polypropylene includes, but is not limited to, polypropylene, impact modified polypropylene, polypropylene-ethylene copolymer, impact modified polypropylene-ethylene copolymer, metallocene polypropylene, metallocene polypropylene-ethylene copolymer, metallocene polypropylene olefin block copolymer (with controlled block sequence), polypropylene-based polyolefin plastomer, polypropylene-based polyolefin elastoplastomer, polypropylene-based polyolefin elastomer, polypropylene-based thermoplastic polyolefin blend, and polypropylene-based thermoplastic elastomer blend. Additionally, polypropylene may be grafted with maleic anhydride. Further, the polyethylenes include, but are not limited to, LDPE, LLDPE, VLDPE, VLLDPE, HDPE, polyethylene-propylene copolymers, metallocene polyethylene, metallocene ethylene-propylene copolymers, and metallocene polyethylene olefin block copolymers (with controlled block sequences), any of which may include grafted compatibilizers or copolymers containing acetate and / or ester groups. As previously discussed, these polyethylenes may be grafted with maleic anhydride. These polyethylenes may also be copolymers and terpolymers containing acetate and / or ester groups, and may be copolymers and terpolymers ionomers containing acetate and / or ester groups.
[0096]
[0112] When relatively large or thick (relative to the foamed cell size) metal pieces are present in the recycled layer of the multi-layer foam structure, undesirable "voids" and "large bubbles" may occur. Therefore, the inclusion of a grafted compatibilizer or a polypropylene and / or polyethylene with copolymers containing acetate and / or ester groups as components may be required to prevent the formation of these undesirable "voids" and "large bubbles".
[0097]
[0113] Additionally, the foam composition fed to the extruder may also contain additional additives compatible with the production of the disclosed multilayer foam structures. Typical additives include, but are not limited to, organic peroxides, antioxidants, extrusion processing aids, other lubricants, heat stabilizers, colorants, flame retardants, antistatic agents, nucleating agents, plasticizers, antibacterial agents, antifungal agents, light stabilizers, UV absorbers, antiblocking agents, fillers, deodorizers, thickeners, cell dimensional stabilizers, metal deactivators, and combinations thereof.
[0098]
[0114] Regardless of how all of the components are fed to the extruder, the shear and mixing within the extruder processing recycled polyolefin material must be sufficient to produce a uniform layer (to the extent that the recycled polyolefin material fed to the extruder is uniform). A co-rotating twin screw extruder can provide sufficient shear and mixing to extrude a layer with uniform properties through the extruder barrel.
[0099] (0115) Specific energy is a measure of how much work is being applied during the extrusion of components and how powerful the extrusion process is. Specific energy can be defined as the energy applied to the material being processed by the extruder, normalized on a per kilogram basis. Specific energy can be quantified in kilowatts of energy applied per hour per kilogram of total feed material. Specific energy is calculated using the formula
number
[0100]
[0116] Specific energy can be used to quantify the amount of shear and mixing of the components in the extruder. The extruders used in the present invention can generate a specific energy of at least 0.090 kW hr / kg, preferably at least 0.105 kW hr / kg, and more preferably at least 0.120 kW hr / kg.
[0101]
[0117] The extrusion temperature of each layer of the multi-layer structure can be at least 10° C. below the onset of thermal decomposition of the chemical blowing (i.e., "expansion") agent. If the extrusion temperature exceeds the decomposition temperature of the blowing agent, the blowing agent will decompose and undesirable "prefoaming" will occur.
[0102] (0118) The foam composition can include a variety of different chemical blowing agents. Examples of chemical blowing agents include, but are not limited to, azo compounds, hydrazine compounds, carbazides, tetrazoles, nitroso compounds, and carbonates. Furthermore, the chemical blowing agents may be used alone or in any combination. In general, the amount of chemical blowing agent can be about the same in the various layers. For example, if one layer has significantly more PPHR chemical blowing agent than another layer (assuming the same chemical blowing agent), the less foamed layer may hinder the expansion of the more foamed layer. Thus, as the multilayer structure heats and foams, problems may arise with the multilayer structure warping, buckling, and / or folding on itself.
[0103] (0119) One chemical blowing agent that can be used in some embodiments is azodicarbonamide ("ADCA"). The amount of ADCA in the foam layer can be about 40% PPHR or less. Thermal decomposition of ADCA typically occurs at about 190-230°C. To prevent thermal decomposition of ADCA in the extruder, the extrusion temperature can be kept at 190°C or less. Another chemical blowing agent that can be used in some embodiments is p-tolylsulfonylhydrazide ("TSH"). The amount of TSH in the foam layer can be about 77% PPHR or less. Another chemical blowing agent that can be used in some embodiments is p-tolylsulfonylsemicarbazide ("TSS"). The amount of TSS in the foam layer can be about 63% PPHR or less. The amount of chemical blowing agent can depend on, among other things, the unfoamed sheet thickness, the desired foam thickness, the desired foam density, the material being extruded, the crosslinking percentage, the type of chemical blowing agent (different blowing agents may generate widely different amounts of gas). However, the amount of blowing agent in each layer should be selected to provide relatively equal foaming in each layer.
[0104]
[0120] When the difference between the decomposition temperature of the thermally decomposable blowing agent and the melting point of the polymer with the highest melting point is large, a catalyst may be used for the blowing agent decomposition. Representative catalysts include, but are not limited to, zinc oxide, magnesium oxide, calcium stearate, glycerin, and urea.
[0105]
[0121] The lower temperature tolerance for extrusion can be the temperature of the polymer with the highest melting point. If the extrusion temperature falls below the melting point of the polymer with the highest melting point, undesirable "unmelts" may appear in the structure. Upon foaming, extruded layers extruded below this lower temperature tolerance may exhibit non-uniform thickness, non-uniform cell structure, collapsed pockets of cells, and other undesirable attributes.
[0106] (0122) The extrusion of non-foamed multilayer sheets (as described in this application) is different from the extrusion of foamed multilayer sheets, which is usually referred to as "extrusion foaming". Extrusion foaming can be performed using physical blowing agents, chemical blowing agents, or a combination thereof. Examples of physical blowing agents are inorganic and organic gases (e.g., nitrogen, carbon dioxide, pentane, butane, etc.) that can be directly injected into the polymer melt under high pressure. As the polyolefin melt exits the extrusion die, these gases nucleate and expand to produce a foamed polymer. Examples of chemical blowing agents (e.g., those previously described in this disclosure) are solids that can decompose exothermically or endothermically at a decomposition temperature to produce a gas. Typical gases produced from chemical blowing agents include nitrogen, carbon dioxide, carbon monoxide, and ammonia, among others. To perform extrusion foaming using chemical blowing agents, the chemical blowing agent can be dispersed in the polyolefin melt and the melt can be heated above the decomposition temperature of the chemical blowing agent while still in the extruder and die. Thus, as the polyolefin melt exits the extrusion die, a foamed polymer can be produced.
[0107]
[0123] Whether the blowing agent is a physical blowing agent, a chemical blowing agent, or a combination thereof, typical extrusion foaming produces polyolefin foam structures with a much rougher surface than comparable foam structures produced by the disclosed method in which an unfoamed multilayer sheet is first co-extruded and foaming occurs after extrusion. The rougher surface of the extruded foam structure is usually caused by larger size cells compared to foams produced by the disclosed method in which an unfoamed multilayer sheet is first co-extruded. Although the cell size and size distribution of the foam structure may not be important in some commercial applications, because surface roughness is a function of cell size, foams with larger cells will be less desirable than foam structures with smaller cells for applications requiring a smooth foam surface.
[0108] (0124) As mentioned above, the surface profile of the foam structure is important in many applications, and therefore extruded foam structures may not be desirable for these applications. Rather, these applications require a smooth foam structure surface to obtain desirable properties, such as ease of lamination to films, fabrics, fiber layers, and / or leather; contact ratio in lamination; and visual aesthetics, among others. A comparison between the surface roughness of extruded foam sheets and the surface roughness of non-extruded foam sheets produced by the methods described herein can be found in the Examples section below. The average surface roughness of the foams produced by the methods described herein can be less than about 80 μm, less than about 70 μm, less than about 50 μm, less than about 40 μm, less than about 30 μm, less than about 25 μm, less than about 20 μm, less than about 15 μm, and less than about 10 μm. The average maximum height (height between the maximum height peak and the maximum depth valley) of foams produced by the methods described herein can be less than about 700 μm, less than about 600 μm, less than about 300 μm, less than about 250 μm, less than about 200 μm, less than about 150 μm, and less than about 100 μm.
[0109]
[0125] The thickness of the non-foamed coextruded multilayer structure can be about 0.1 to about 30 mm, preferably about 0.2 to about 25 mm, more preferably about 0.3 to about 20 mm, and even more preferably about 0.4 to about 15 mm. Furthermore, the thickness of any individual layer, including the recycled layer(s) and the non-recycled layer(s) in the non-foamed coextruded multilayer structure can be at least about 0.05 mm, preferably at least about 0.1 mm, more preferably at least about 0.15 mm, and even more preferably at least about 0.2 mm.
[0110]
[0126] In embodiments where a layer or layers of a multi-layer structure are not intended to be foamed (e.g., where the layer is a "skin" or "film" layer), the non-foamed layer or layers can be thin and easily flexible so that when melted, they do not significantly impede the expansion of the foam layer or layers during the foaming process. Physical properties of the non-foamed layer or layers that may impede the expansion of the foam layer or layers include, but are not limited to, the thickness, flexibility, melt strength, and crosslink percentage of the non-foamed layer. Similarly, the thickness, flexibility, melt strength, and crosslink percentage of the foam layer or layers and the final thickness and density of the foam layer or layers may also affect whether the non-foamed layer or layers impede the expansion of the foam layer or layers.
[0111]
[0127] In general, the thickness of the non-foamed layer(s) can be preferably about 20% or less of the thickness of the entire coextruded non-foamed structure. If the thickness of the non-foamed layer(s) is greater than about 20% of the total thickness of the coextruded non-foamed structure, problems may occur with the multilayer structure warping, buckling, and / or folding on itself as the multilayer structure heats and foams. In contrast, there is no limit to how thin the thickness of the non-foamed layer(s) can be in relation to the entire non-foamed coextruded multilayer structure. For example, the non-foamed layer(s) can be as thin as about 0.1 μm (i.e., a thin tie layer of typical thickness used in multilayer flexible packaging and barrier films).
[0112]
[0128] After the coextruded multilayer structure is produced by the extruder, the coextruded structure can be subjected to irradiation with ionizing radiation at a given exposure to crosslink the composition of the coextruded structure, thereby obtaining an irradiation crosslinked multilayer structure. Ionizing radiation often fails to produce a sufficient degree of crosslinking for polypropylene(s), polypropylene-based materials, some polyethylene(s), and some polyethylene-based materials. Therefore, crosslinking promoters can usually be added to the foam composition fed to the extruder to promote crosslinking. Polymers crosslinked by ionizing radiation are commonly referred to as "physically crosslinked".
[0113]
[0129] Physical crosslinking is distinct from chemical crosslinking, in which crosslinking can be produced using crosslinking accelerators, but without the use of ionizing radiation. Chemical crosslinking typically involves the use of peroxides, silanes, or vinyl silanes. During peroxide crosslinking processes, crosslinking typically occurs in the extrusion die. In contrast, in silane and vinyl silane crosslinking processes, crosslinking typically occurs during a secondary operation after extrusion, where crosslinking of the extruded material can be accelerated by heat and moisture.
[0114]
[0130] Regardless of the chemical crosslinking step, chemically crosslinked foam structures typically exhibit a much rougher surface than comparable foam structures produced by the disclosed methods of physical crosslinking. The rougher surface of chemically crosslinked foam structures is typically caused by larger sized cells compared to foams produced by the disclosed methods using physical crosslinking. Although the cell size and size distribution of the foam structure may not be critical for some commercial applications, foams with larger cells will be less desirable than foam structures with smaller cells for applications requiring a smooth foam surface, since surface roughness is a function of cell size.
[0115] (0131) As mentioned above, the surface profile of the foam structure is important in many applications, and therefore, chemically crosslinked structures are not desirable for these applications. Rather, these applications require a smooth foam structure surface to obtain desirable properties, such as ease of lamination to films, fabrics, fiber layers, and / or leather; contact ratio in lamination; and visual aesthetics, among others. A comparison between the surface roughness of chemically crosslinked chemically crosslinked sheets and the surface roughness of physically crosslinked sheets produced by the methods described herein can be seen in the Examples section below.
[0116] (0132) Examples of ionizing radiation include, but are not limited to, alpha rays, beta rays, gamma rays, and electron beams. Among them, it is preferable to use an electron beam having uniform energy to prepare a crosslinked multilayer structure. The exposure time, frequency, and acceleration voltage during irradiation with an electron beam can be varied over a wide range depending on the desired crosslinking degree and thickness of the coextruded multilayer structure. However, the ionizing radiation should usually be in the range of about 10 to about 500 kGy, preferably about 20 to about 300 kGy, and more preferably about 20 to about 200 kGy. If the exposure is too low, cell stability may not be maintained during foaming. If the exposure is too strong, the moldability of the resulting multilayer foam structure may be insufficient. (Moldability may be a desirable property when the multilayer foam structure is used for thermoforming applications). In addition, the non-foamed multilayer structure may soften due to heat release due to heat generation when exposed to electron beam irradiation, and as a result, if the exposure is too strong, the structure may deform. In addition, the polymer component may also decompose due to excessive polymer chain scission.
[0117]
[0133] The coextruded non-foamed multilayer structure may be irradiated up to 4 times, preferably 2 times or less, and more preferably only 1 time. If the irradiation frequency is more than about 4 times, the polymer components may be degraded, and in that case, for example, the resulting foam layer will not produce uniform cells during foaming.
[0118]
[0134] When the thickness of the coextruded multilayer structure is greater than about 4 mm, irradiation of each primary surface of the multilayer profile with ionizing radiation may be preferred to achieve a uniform degree of crosslinking in the primary surface(s) and inner layer(s).
[0119] (0135) Irradiation with electron beams is advantageous in that coextruded structures with various thicknesses can be effectively crosslinked by controlling the electron acceleration voltage. The acceleration voltage can usually be in the range of about 200 to about 1500 kV, preferably about 400 to about 1200 kV, and more preferably about 600 to about 1000 kV. If the acceleration voltage is less than about 200 kV, the irradiation may not reach the inner part of the coextruded structure. As a result, the cells in the inner part may become coarse and uneven during foaming. Furthermore, too low an acceleration voltage for a given thickness profile may cause arcing and generate "pinholes" or "tunnels" in the foamed multilayer structure. On the other hand, if the acceleration voltage is greater than about 1500 kV, the polymer may decompose.
[0120]
[0136] Regardless of the type of ionizing radiation selected, crosslinking can be effected and the composition of the coextruded structure can be about 20 to about 75%, preferably about 30 to about 60%, crosslinked, as measured by the "Toray Gel Fraction Percentage Method."
[0121]
[0137] According to the "Toray Gel Fraction Percentage Method," the non-crosslinked components in the composition are dissolved using tetralin solvent. In principle, the non-crosslinked material is dissolved in tetralin, and the degree of crosslinking is expressed as the weight percent of the crosslinked material in the total composition.
[0122] (0138) The equipment used to measure the percent polymer crosslinking includes 100 mesh (0.0011 cm (0.0045 in) wire diameter); sus 304 stainless steel bag; wire and clips; Miyamoto thermostatic oil bath apparatus; analytical balance; fume hood; gas burner; high temperature oven; antistatic gun; and three 3.5 liter wide-mouth stainless steel containers with lids. The reagents and materials used include tetralin high molecular weight solvent, acetone, and silicone oil. Specifically, the empty wire mesh bag is weighed and the mass is recorded. For each sample, approximately 100 milligrams ± approximately 5 milligrams of sample is weighed and transferred to the wire mesh bag. The mass of the wire mesh bag and sample (usually foam shreds) is recorded. Each bag is attached to the corresponding wire and clips. When the solvent temperature reaches 130°C, the bundle (bag and sample) is immersed in the solvent. Shake the sample up and down about 5 or 6 times to release all air bubbles and thoroughly wet the sample. Place the sample on a stirrer and stir for 3 hours to allow the solvent to dissolve the foam. Then cool the sample in a fume hood. Wash the sample in a container with primary acetone by shaking it up and down about 7 or 8 times. Wash the sample a second time in a second acetone wash. Wash the washed sample again as above in a third container of fresh acetone. Then hang the sample in a fume hood for about 1 to about 5 minutes to allow the acetone to evaporate. Next, dry the sample in a drying oven at 120°C for about 1 hour. Cool for at least about 15 minutes. Weigh the wire mesh bag on an analytical balance and record the mass.
[0123]
[0139] The degree of crosslinking can then be calculated using the formula 100*(CA) / (BA), where A=mass of the empty wire mesh bag, B=mass of the wire bag + mass of the foam sample before immersion in tetralin, and C=mass of the wire bag + mass of the dissolved sample after immersion in tetralin.
[0124]
[0140] Suitable cross-linking agents include, but are not limited to, commercially available di-, tri-, tetra-, penta-, and higher functional monomers. Such cross-linking monomers are available in liquid, solid, pellet, and powder form. Examples include, but are not limited to, acrylates or methacrylates such as 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, tetramethylolmethane triacrylate, 1,9-nonanediol dimethacrylate and 1,10-decanediol dimethacrylate; allyl esters of carboxylic acids (e.g., trimellitic acid triallyl ester, pyromellitic acid triallyl ester, and oxalic acid diallyl ester); allyl esters of cyanuric acid or isocyanuric acid such as triallyl cyanurate and triallyl isocyanurate; maleimide compounds such as N-phenylmaleimide and N,N'-m-phenylene bismaleimide; compounds having at least two triple bonds such as dipropargyl phthalate and dipropargyl maleate.Furthermore, such crosslinkers may be used alone or in any combination. The amount of crosslinker in a layer composition can vary depending on, among other things, the molecular weight, functional group, and crosslinking efficiency of the crosslinker and the dose of ionizing radiation. Divinylbenzene (DVB), a bifunctional liquid crosslinking monomer, can be used as a crosslinker in the present invention and can be added to the extruder at a level of about 4% PPHR or less, preferably about 2% to about 3.5% PPHR. Some polymers crosslink more easily than others. Thus, a layer containing a polymer that is more prone to crosslinking may have less crosslinker than a layer containing a polymer that is less prone to crosslinking. In some embodiments, one layer can be intentionally crosslinked more than another layer, which may require the addition of more crosslinker to promote more crosslinking.
[0125]
[0141] Crosslinks may be achieved using a variety of different techniques and can be formed both intermolecularly between different polymer molecules and intramolecularly between portions of a single polymer molecule. Such techniques include, but are not limited to, providing a crosslinker separate from the polymer chain and providing a polymer chain incorporating a crosslinker that includes functional groups capable of forming crosslinks or that can be activated to form crosslinks.
[0126]
[0142] After irradiation of the extruded structure, foaming may be performed by heating the crosslinked multilayer structure at a temperature higher than the decomposition temperature of the thermally decomposable foaming agent. For the thermally decomposable foaming agent azodicarbonamide, foaming may be performed in a continuous process at about 200 to about 260°C, preferably about 220 to about 240°C. A continuous foaming process may be preferred over a batch process for producing a continuous foamed sheet.
[0127]
[0143] Foaming can usually be performed by heating the crosslinked multilayer structure using molten salt, radiant heaters, vertical hot air ovens, horizontal hot air ovens, microwave energy, or a combination thereof. Foaming can also be performed, for example, by an injection step using nitrogen in an autoclave followed by free foaming using molten salt, radiant heaters, vertical hot air ovens, horizontal hot air ovens, microwave energy, or a combination of these methods. A preferred combination of molten salt and radiant heaters can be used to heat the crosslinked multilayer structure. In particular, the irradiated extruded structure that is not in contact with the molten salt can be heated by a radiant heater.
[0128]
[0144] If desired, the crosslinked structure can be preheated to soften it prior to foaming, which can help stabilize the expansion of the structure during foaming.
[0129]
[0145] The density of the multilayer foam structure can be defined and measured using the section density or the "whole" density, not the "core" density, according to JIS K6767. The multilayer foam structure produced using the above method has a density of about 20 to about 250 kg / m 3 , preferably about 30 kg / m 3 ~Approx. 125kg / m 3This can provide a foam having a section, or "whole" density of about 20 kg / m. The section density can be controlled by the amount of blowing agent and the thickness of the coextruded structure. 3 If the density of the structure is less than about 20 kg / m, the structure cannot be efficiently foamed because a large amount of chemical foaming agent is required to obtain the density. 3 If the density of the multi-layer foam structure is less than about 20 kg / m, it may become increasingly difficult to control the expansion of the structure during the foaming step. 3 If it is less than this, the foam structure will gradually become more susceptible to bubble collapse. Therefore, it is recommended to use a pressure of about 20 kg / m 3 At densities below this, it can be difficult to produce multi-layer foam structures (with or without recycled materials) of uniform section density and thickness.
[0130] (0146) The multi-layer foam structure has a strength of about 250 kg / m 3 Not limited to a section density of at least about 350 kg / m 3 , about at least 450 kg / m 3 , or about at least 550 kg / m 3 However, since higher densities can generally be cost-prohibitive when compared to other materials that may be used for a given application, multi-layer foam structures are generally manufactured with densities of about 250 kg / m 3 It may be preferable to have a density less than 1000 nm.
[0131]
[0147] The various foam layers (with or without recycled polyolefin material) in the multi-layer foam structure can have similar densities. These densities can be determined and controlled by the amount of chemical blowing agent(s), the type(s) of chemical blowing agent(s), the thickness of each coextruded non-foamed layer(s), and / or the overall thickness of the coextruded non-foamed multi-layer structure. If the individual foam layers have densities that differ significantly from one another, problems can arise with the multi-layer foam structure warping, buckling, and / or folding on itself as the multi-layer structure is heated and foamed. The densities of the foam layers can be within about 15% of each other, preferably within about 10% of each other, and more preferably within about 5% of each other.
[0132]
[0148] The multilayer foam structure produced using the above method may have closed cells. Preferably, at least 90% of the cells, preferably at least 95% of the cells, and more preferably greater than 98% of the cells have intact cell walls. The average cell size may be from about 0.05 to about 1.0 mm, preferably from about 0.1 to about 0.7 mm. When the average cell size is less than about 0.05 mm, the density of the multilayer foam structure is typically less than 250 kg / m 3 The average cell size may be larger than 1 mm. If the average cell size is larger than 1 mm, the foam may have an uneven surface. Also, if the cell population in the foam is not of the preferred average cell size, the foam structure may tear, which is undesirable. This occurs when the foam structure is stretched or a portion of the foam structure is subjected to a secondary process. The cell size in the multilayer foam structure may have a bimodal distribution, which represents a cell population in the core of the foam structure that is relatively round, and a cell population in a skin near the surface of the foam structure that is relatively flat, thin, and / or elliptical in shape.
[0133] (0149) The thickness of the multilayer foam structure can be about 0.2 to about 50 mm, preferably about 0.4 to about 40 mm, more preferably about 0.6 to about 30 mm, and even more preferably about 0.8 to about 20 mm. If the thickness is less than about 0.2 mm, the foaming may not be efficient due to large gas loss from the primary surface. If the thickness is more than about 50 mm, it may become increasingly difficult to control the expansion during the foaming step. Therefore, it may become increasingly more difficult to produce a multilayer foam structure (with or without recycled material) of uniform section density and thickness.
[0134]
[0150] The desired thickness can also be obtained by secondary processes such as cutting, skiving, or joining. Cutting, skiving, or joining can produce thicknesses ranging from about 0.1 mm to about 100 mm.
[0135]
[0151] In embodiments where the layer(s) of the multi-layer structure are not intended to be foamed, the thickness of the non-foamed layer(s) may be reduced when the multi-layer structure is foamed. This can be achieved by expanding the foam layer(s) and thus stretching the non-foamed layer(s). Thus, for example, when the multi-layer structure is expanded to twice its original area, the thickness of the non-foamed layer(s) can be expected to be approximately half. Furthermore, when the multi-layer structure is expanded to four times its original area, the thickness of the non-foamed layer(s) can be expected to be reduced to approximately ¼ of its original thickness.
[0136] (0152) The disclosed multilayer foam structures can be used in a variety of applications. One such application is as foam tape and gasket material. Closed-cell foam tapes are typically used in areas such as window glass installation, where a foam tape strip is placed between two panes of window glass to seal the air between the panes. This improves the insulating properties of the window. The foam also acts as a cushion for the pane from the effects of thermal expansion and contraction of the building and the window frame resulting from daily and seasonal temperature fluctuations. Similarly, closed-cell foam gaskets are typically used for sealing and cushioning purposes. Handheld electronic devices and home appliances are two examples that may include foam gaskets. Soft, flexible foam structures are typically suitable for tapes or gaskets.
[0137]
[0153] When the multilayer foam structure is used as a tape or gasket, a pressure-sensitive adhesive layer may be disposed on at least a portion of one or both of the major surfaces. Any pressure-sensitive adhesive known in the art may be used. Examples of such pressure-sensitive adhesives include, but are not limited to, acrylic polymers, polyurethanes, thermoplastic elastomers, block copolymers, polyolefins, silicones, rubber-based adhesives, copolymers of ethylhexyl acrylate and acrylic acid, copolymers of isooctyl acrylate and acrylic acid, blends of acrylic adhesives and rubber-based adhesives, and combinations of the foregoing.
[0138] (0154) The multi-layer foam structure can also be thermoformed. To thermoform the multi-layer foam structure, the foam can be heated to the melting point of the polyolefin blend for all layers in the multi-layer foam structure. If any layer is an immiscible polymer, the multi-layer foam structure can exhibit more than one melting point. In this case, the multi-layer foam structure can usually be thermoformed when the foam is heated to a temperature intermediate between the lowest and highest melting points of the multi-layer foam composition. Furthermore, the multi-layer foam structure can be thermoformed onto a substrate such as rigid polypropylene, ABS, or wood fiber composite. Preferably, the multi-layer foam structure can be thermoformed onto a substrate such that the non-recycled foam layer side of the multi-layer foam faces the substrate. The substrate itself can also be thermoformed simultaneously as the multi-layer foam structure. Furthermore, the substrate can be facing the non-recycled foam layer side (i.e., the surface) of the multi-layer foam.
[0139]
[0155] One example of a thermoformed product is an air duct for an automobile. A closed cell foam structure may be particularly suited for this application due to its lower mass (compared to solid plastics), its insulating properties that help maintain the temperature of the air flowing through the duct, and its resistance to vibration (versus solid plastics). Thus, a rigid multi-layer foam structure may be suitable for an automobile air duct.
[0140] (0156) In some embodiments, the multilayer foam structure is a laminate comprising a multilayer foam and a laminate layer. Preferably, the laminate can be oriented on the non-recycled foam layer side (i.e., the surface) of the multilayer foam. In these laminates, the multilayer foam structure can be combined with, for example, a film and / or a foil. Examples of suitable materials for such layers include, but are not limited to, polyvinyl chloride (PVC); thermoplastic polyolefin (TPO); thermoplastic urethane (TPU); fabrics such as polyester, polypropylene, cloth and other fabrics; and fiber layers such as leather and / or nonwoven fabrics. Such layers can be manufactured using standard techniques well known to those skilled in the art. Importantly, the multilayer foam of the present disclosure can be laminated to one or both sides of these materials and can include multiple other layers. If the multilayer foam is laminated on both sides, preferably, these laminate layers can be oriented on the non-recycled foam layer side of the multilayer foam.
[0141]
[0157] In these laminates, one layer may be joined to an adjacent layer by chemical bonds, mechanical means, or a combination of these. Adjacent laminate layers may also be secured to one another by any other means including the use of opposing electromagnetic charges or the attractive forces that exist between materials that both have predominantly hydrophobic or predominantly hydrophilic properties.
[0142] (0158) In some embodiments, the multilayer foam structures or laminates are used in automotive interior parts such as door panels, door rolls, door inserts, door stuffers, trunk stuffers, arm rests, center consoles, seat cushions, seat backs, head rests, seat back panels, instrument panels, knee bolsters, headliners, etc. These multilayer foam structures or laminates can also be used in furniture (e.g., commercial, office, and residential furniture) such as chair cushions, chair backs, sofa cushions, sofa trims, recliner cushions, recliner trims, couch cushions, couch trims, sleeper cushions, or sleeper trims. These multilayer foam laminates or structures can also be used in walls such as modular walls, movable walls, wall panels, modular panels, office system panels, partitions, or mobile partitions. The multilayer foam laminates or structures can also be used in storage cases (e.g., commercial, office, and residential) that can be mobile or stationary. Additionally, the multi-layer foam laminates and structures can also be used in covers such as chair cushion covers, chair back covers, armrest covers, sofa covers, couch cushion covers, recliner cushion covers, recliner covers, couch cushion covers, couch covers, sleeper cushion covers, sleeper covers, wall covers, and architectural covers.
[0143]
[0159] Some embodiments include a first layer of the disclosed multilayer foam structure and a second layer selected from the group consisting of solid hardwood floor panels, engineered wood floor panels, laminate floor panels, vinyl floor tiles, ceramic floor tiles, porcelain floor tiles, stone floor tiles, quartz floor tiles, cement floor tiles, and concrete floor tiles. As mentioned above, preferably, the second layer(s) can be oriented toward the non-recycled layer(s) side (i.e., face) of the multilayer foam structure.
[0144]
[0160] In these laminates, the first layer may be joined to the adjacent panel or tile by chemical bonds, mechanical means, or a combination thereof. Adjacent laminate layers may also be secured to one another by any other means including the use of opposing electromagnetic charges or the attractive forces that exist between materials that both have predominantly hydrophobic or predominantly hydrophilic properties.
[0145]
[0161] A common method of adhering the disclosed multi-layer foam to floor panels, particularly solid hardwood floor panels, engineered wood floor panels, and laminate floor panels, can be through a pressure-sensitive adhesive layer that can be disposed on at least a portion of the foam surface and / or panel surface. Preferably, the adhesive layer can be disposed on the surface of the non-recycled layer of the multi-layer foam structure. Any pressure-sensitive adhesive known in the art can be used. Examples of such pressure-sensitive adhesives are acrylic polymers, polyurethanes, thermoplastic elastomers, block copolymers, polyolefins, silicones, rubber-based adhesives, copolymers of ethylhexyl acrylate and acrylic acid, copolymers of isooctyl acrylate and acrylic acid, blends of acrylic adhesives and rubber-based adhesives, and combinations of the foregoing.
[0146] (0162) Multi-layer foam bonded to floor panels, particularly solid hardwood floor panels, engineered wood floor panels, and laminate floor panels, serves several purposes. The foam can reduce the reflected sound pressure level when the panel is impacted, for example, when walking on the panel in boots or high heels. The foam can also act as a water vapor barrier between the panel and the subfloor, and aid in more uniform laying between multiple panels, as any unevenness, bumps, or spikes on the subfloor (e.g., protruding nail heads) are buffered by the foam. These floor panels and tiles are commonly installed in homes, office buildings, and other commercial buildings.
[0147]
[0163] Another embodiment of the present invention provides a flooring system including an upper floor layer, a sub-floor layer, and one or more intermediate layers, wherein at least one intermediate layer includes the disclosed multi-layer foam structure disposed between the sub-floor and the upper floor layer. Preferably, the sub-floor and the upper floor layer can be oriented on the non-recycled layer side / surface of the multi-layer foam structure.
[0148]
[0164] In this system, the foam layer may or may not be bonded to any adjacent layers, including the subfloor or overfloor layers. If any layers of the disclosed system are bonded, the adhesion may be by chemical bonding, mechanical means, or a combination thereof. Adjacent layers may also be secured to one another by any other means, including the use of opposing electromagnetic charges or the attractive forces that exist between materials that both have predominantly hydrophobic or predominantly hydrophilic properties.
[0149]
[0165] If any layers are bonded, the general method of bonding can be a one-part urethane adhesive, a two-part urethane adhesive, a one-part acrylic adhesive, or a two-part acrylic adhesive. The adhesives can be applied during installation of the system in homes, office buildings, and commercial buildings.
[0150] (0166) The foam in this system serves several purposes. It can reduce the reflected sound pressure levels when the upper floor layer is impacted, for example, when walking on the panel with boots or high heels. It also acts as a water vapor barrier between the panel and the subfloor, helping to create a more uniform laydown between multiple panels, as any unevenness, bumps, or spikes on the subfloor (e.g., nail heads sticking out) are buffered by the foam. In cases where the upper floor layer is comprised of ceramic, porcelain, stone, quartz, cement, and concrete floor tiles interlocked by grout, and all layers in the flooring system are bonded, the foam can help reduce grout failure by buffering the variable thermal expansion and contraction of the various layers of the system.
[0151]
[0167] To meet the requirements of any of the above applications, the disclosed structures of the present disclosure may be subjected to various secondary processes including, but not limited to, embossing, corona or plasma treatment, surface roughening, surface smoothing, perforating or microperforating, splicing, cutting, skiving, layering, bonding, and drilling.
[0152] (0168) Working Example The following table lists the various ingredients used in the following examples and a description of those ingredients. [Table 1] TIFF2025026848000004.tif69150 (All examples in this disclosure were coextruded using a feedblock manifold)
[0153]
[0169] Example 1 - A / B Product, A=Foam and B=Film Component A (i.e., foam layer components) including resins (50 wt% Infuse™ OBC9107, 40 wt% 6232, and 10 wt% Adflex™ Q100F), chemical blowing agent (7.5% PPHR ADCA), crosslinking accelerator (2.5% PPHR DVB), antioxidant (5.5% PPHR PR023), and processing aid (2.0% PPHR TPM11166) was fed to a first extruder. The first extruder extruded component A at a specific energy of 12.1 kW·hr / kg and a temperature of 173°C. Component B (i.e., film layer components) containing resin (100% by weight Adflex™ Q100F), antioxidant (2.75% PPHR PR023), and processing aid (2.0% PPHR TPM11166) was fed to a second extruder. As the first extruder extruded component A, the second extruder simultaneously extruded component B at a specific energy of 39.2 kW·hr / kg and a temperature of 201 °C.
[0154]
[0170] Components A and B were coextruded using an 80 / 20 feedblock manifold to produce a non-crosslinked, non-foamed multilayer sheet approximately 1.33 mm thick (the non-foamed A layer is approximately 0.97 mm thick, and the non-foamed B layer is approximately 0.36 mm thick). FIG. 1C is a backlit magnified photograph of a thin section of the non-foamed multilayer sheet. After coextrusion, the sheet was crosslinked by electron beam irradiation at a dose of 45 kGy with the component B layer (i.e., the film layer) facing the radiation source. Furthermore, the irradiation voltage (650 kV) was selected so that the exposure was approximately uniform throughout the depth of the sheet.
[0155]
[0171] After crosslinking, both sides of the sheet were heated to about 232°C (450°F) to an average thickness of 3.98 mm and 0.102 g / cm 3 A multilayer foam structure was obtained with an average overall density of 1.0 μm. The foam layer was about 3.88 mm thick, and the film layer was about 0.10 mm thick. Furthermore, the overall average gel fraction (crosslink percentage) of the multilayer foam structure was 45.7%. FIG. 1A is a backlit magnified photograph of a thin slice of the foam of Example 1. FIG. 1B is a frontlit non-magnified photograph of a thin slice of the foam of Example 1. In both of FIGS. 1A-1B, the skin layer is visible.
[0156]
[0172] Example 2 - A / B Product, A=Foam and B=Foam Component A (i.e., first foam layer components) including resins (50 wt% Infuse™ OBC9107, 40 wt% 6232, and 10 wt% Adflex™ Q100F), chemical blowing agent (7.5% PPHR ADCA), crosslinking accelerator (2.5% PPHR DVB), antioxidant (5.5% PPHR PR023), and processing aid (2.0% PPHR TPM11166) was fed to a first extruder. The first extruder extruded component A at a specific energy of 11.5 kW·hr / kg and a temperature of 173°C. Component B (i.e., second foam layer component), including resins (40 wt.% 7250FL, 32.5 wt.% 6232, 15 wt.% Adflex™ Q100F, 12.5 wt.% LLP8501.67), chemical blowing agent (7.5% PPHR ADCA), crosslinking accelerator (2.75% PPHR DVB), antioxidant (5.0% PPHR PR023), and processing aid (2.0% PPHR TPM11166), was fed to the second extruder. As the first extruder extruded component A, the second extruder simultaneously extruded component B at a specific energy of 15.5 kW·hr / kg and a temperature of 168°C.
[0157]
[0173] Components A and B were coextruded using an 80 / 20 feedblock manifold to produce a non-crosslinked, non-foamed multilayer sheet approximately 1.05 mm thick (the non-foamed A layer is approximately 0.80 mm thick, and the non-foamed B layer is approximately 0.25 mm thick). FIG. 2C is a backlit magnified photograph of a thin section of the non-foamed multilayer sheet. After coextrusion, the sheet was crosslinked by electron beam irradiation at a dose of 45 kGy with the component B layer (i.e., the second foam layer) facing the radiation source. Furthermore, the irradiation voltage (650 kV) was selected such that the exposure was approximately uniform throughout the depth of the sheet.
[0158]
[0174] After crosslinking, both sides of the sheet were heated to about 232°C (450°F) to an average thickness of 2.24 mm and 0.133 g / cm 3The multi-layer foam structure had an average overall density of about 1.61 mm. The first foam layer was about 1.61 mm thick, and the second foam layer was about 0.63 mm thick. Furthermore, the overall average gel fraction (crosslink percentage) of the multi-layer foam structure was 46.7%. Figure 2A is a backlit magnified photograph of a thin slice of the foam of Example 2. Figure 2B is a frontlit unmagnified photograph of a thin slice of the foam of Example 2.
[0159]
[0175] Example 3 - A / B / A Product, A=Foam and B=Foam Containing Recycled Metallized Polyolefin Material Component A (i.e., the first and third foam layer components) containing resins (40 wt.% 7250FL, 32.5 wt.% 6232, 15 wt.% Adflex™ Q100F, 12.5 wt.% LLP8501.67), chemical blowing agent (7.5% PPHR ADCA), crosslinking accelerator (2.75% PPHR DVB), antioxidant (5.0% PPHR PR023), and processing aid (2.0% PPHR TPM11166) were fed to the first and third extruders. The first and third extruders extruded component A at a specific energy of 18.3 kW·hr / kg and a temperature of 172 °C. Component B (i.e., the second recycled foam layer component), which contained resins (40 wt% 7250FL, 32.5 wt% 6232, 15 wt% recycled resin, 12.5 wt% LLP8501.67), chemical foaming agent (7.5% PPHR ADCA), crosslinking accelerator (2.75% PPHR DVB), antioxidant (5.0% PPHR PR023), and processing aid (2.0% PPHR TPM11166), was fed to the second extruder. As the first and third extruders extruded component A, the second extruder simultaneously extruded component B at a specific energy of 16.4 kW·hr / kg and a temperature of 169 °C.
[0160]
[0176] Components A and B were coextruded using a 25 / 50 / 25 feedblock manifold to produce a non-crosslinked, non-foamed multilayer sheet approximately 1.04 mm thick (the non-foamed A layers are approximately 0.26 and 0.28 mm thick, and the non-foamed B layers are approximately 0.50 mm thick). FIG. 3E is a backlit magnified photograph of a thin section of the non-foamed multilayer sheet. After coextrusion, the sheet was crosslinked by electron beam irradiation at a radiation dose of 45 kGy. Additionally, the irradiation voltage (650 kV) was selected such that the exposure was approximately uniform throughout the depth of the sheet.
[0161]
[0177] After crosslinking, both sides of the sheet were heated to about 232°C (450°F) to an average thickness of 2.05 mm and 0.208 g / cm 3 A multilayer foam structure was obtained with an average overall density of 1.06 mm. The first and third foam layers sandwiched the second recycled foam layer. The first and third foam layers had a combined thickness of about 1.06 mm (each about 0.53 mm), and the second recycled foam layer had a thickness of about 0.99 mm. Furthermore, the multilayer foam structure had an overall average gel fraction (crosslink percentage) of 43.2%. Figures 3A-3B are backlit magnified photographs of thin slices of the foam of Example 3. Figures 3C-3D are frontlit unmagnified photographs of thin slices of the foam of Example 3.
[0162]
[0178] Example 4 - A / B / A Product, A=Foam and B=Foam containing recycled cryogenically ground foam material Component A (i.e., the first and third foam layer components) containing resins (40 wt.% 7250FL, 32.5 wt.% 6232, 15 wt.% Adflex™ Q100F, 12.5 wt.% LLP8501.67), chemical blowing agent (7.5% PPHR ADCA), crosslinking accelerator (2.75% PPHR DVB), antioxidant (5.0% PPHR PR023), and processing aid (2.0% PPHR TPM11166) were fed to the first and third extruders. The first and third extruders extruded component A at a specific energy of 18.3 kW·hr / kg and a temperature of 172 °C. Component B (i.e., the second recycled foam layer component), containing resins (40 wt% 7250FL, 32.5 wt% 6232, 15 wt% recycled crosslinked foam, 12.5 wt% LLP8501.67), chemical foaming agent (7.5% PPHR ADCA), crosslinking accelerator (2.75% PPHR DVB), antioxidant (5.0% PPHR PR023), and processing aid (2.0% PPHR TPM11166), was fed to the second extruder. As the first and third extruders extruded component A, the second extruder simultaneously extruded component B at a specific energy of 17 kW·hr / kg and a temperature of 170 °C.
[0163]
[0179] Components A and B were coextruded using a 25 / 50 / 25 feedblock manifold to produce a non-crosslinked, non-foamed multilayer sheet approximately 1.11 mm thick (the non-foamed A layers are approximately 0.26 and 0.25 mm thick, and the non-foamed B layers are approximately 0.60 mm thick). FIG. 4C is a backlit magnified photograph of a thin section of the non-foamed multilayer sheet. After coextrusion, the sheet was crosslinked by electron beam irradiation at a radiation dose of 45 kGy. Additionally, the irradiation voltage (650 kV) was selected such that the exposure was approximately uniform throughout the depth of the sheet.
[0164]
[0180] After crosslinking, both sides of the sheet were heated to about 232°C (450°F) to an average thickness of 3.60 mm and 0.130 g / cm 3The multi-layer foam structure had an average overall density of 1.01 mm. The first and third foam layers sandwiched the second recycled foam layer. The first and third foam layers had a combined thickness of about 1.90 mm (each about 0.95 mm), and the second recycled foam layer had a thickness of about 1.70 mm. Furthermore, the overall average gel fraction (crosslinked percentage) of the multi-layer foam structure was 37.9%. FIG. 4A is a backlit magnified photograph of the foam of Example 4. FIG. 4B is a frontlit unmagnified photograph of the foam of Example 4. Note that in Example 4, the recycled crosslinked foam material is charcoal in color, which is the reason for the dark color of the middle layer.
[0165] (0181) Extrusion Foaming vs. Post-Extrusion Foaming Extruded polyethylene foam sheet (0.0025-0.026 g / cm, commercially available from Gladon Company, Oak Creek, WI) 3 Pool liner wall foam ("38064 blue Gladon") was laminated with two sheets of 0.025-0.026 g / cm 3The polyethylene foam sheets of the three examples were compared. The first sheet was Toraypef® 40100-AG00, commercially produced by Toray Industries, Inc. (Shiga Prefecture, Japan). 40100-AG00 was foamed by heating an irradiation cross-linked sheet with hot air. The second sheet was Toraypef® 40064LCE-STD, manufactured by Toray Plastics (America), Inc. 40064LCE-STD was foamed by heating one surface of an irradiation cross-linked sheet with molten salt and the other surface with radiant heat. The surface properties of these three examples were tested using a Nanovea ST400 3D surface meter. The probe specifications and measurement parameters are shown in Tables 2 and 3 below. As shown in Table 4 below, regardless of heating method, the extruded foam material (38064 blue Gladon) (exhibiting an average surface roughness (Sa) of 83.9 μm and a maximum height (height between the highest peak and deepest valley) (Sz) of 706 μm) is significantly rougher than the extruded foam sheets (40100-AG00 and 40064LCE-STD) (exhibiting an average surface roughness (Sa) of 20.7 to 65.2 μm and a maximum height (Sz) of 237 to 592 μm).
[0166] (0182) 0.067g / cm 3 The surface of a chemically crosslinked polyolefin foam sheet (ProGame™ XC-Cut 7010, commercially produced by the Trocellen Group of Companies) was coated with two 0.067 g / cm 3The surfaces of the physically crosslinked polypropylene / polyethylene blend foam sheets (Toraypef® 15030AC17-STD and ToraSoft® 15030SR18-STD) of the three examples were compared. Both the chemically crosslinked and physically crosslinked foams were foamed in a post-extrusion process. The surface properties of these three examples were tested using a Nanovea ST400 3D surface gauge. The probe specifications and measurement parameters are shown in Tables 2 and 3 below. As shown in Table 4 below, the chemically crosslinked foam (XC-Cut7010) exhibited a surface roughness (Sa) of 89.5 μm and a maximum height (Sz) of 856 μm. The physically crosslinked foam exhibited a surface roughness (Sa) of 7.63 to 23.9 μm and a maximum height (Sz) of 81.0 to 273 μm. Thus, the physically crosslinked foam exhibits a significantly smoother surface than the chemically crosslinked foam. [Table 2] [Table 3] [Table 4]
[0167] (0183) Test Method Various properties of the above examples were measured by the following methods. The specific energy of the extruder is given by the formula
number
[0168]
[0186] The "density" of a multilayer foam structure can be defined and measured using section density or "whole" density, not "core" density, in accordance with JIS K6767. In general, the preferred value of density is 20 to 250 kg / m 3 , more preferably 30 to 125 kg / m 3 It would be.
[0169]
[0187] The "average surface roughness" and "maximum height" (height between the highest peak and deepest valley) of the multilayer foam structure surface can be defined and measured using a Nanovea 3D Non-Contact profilometer. Probe specifications and measurement parameters for measuring the average surface roughness and maximum height can be found in Tables 2 and 3 below. The average surface roughness of the produced foam can be less than about 80 μm, less than about 70 μm, less than about 50 μm, less than about 40 μm, less than about 30 μm, less than about 25 μm, less than about 20 μm, less than about 15 μm, and less than about 10 μm. The maximum height of the produced foam can be less than about 700 μm, less than about 600 μm, less than about 300 μm, less than about 250 μm, less than about 200 μm, less than about 150 μm, and less than about 100 μm.
[0170] (0188) "Cross-linking" can be measured according to the "Toray Gel Fraction Method," in which tetralin solvent is used to dissolve the non-cross-linked components. In principle, the non-cross-linked material is dissolved in tetralin, and the degree of cross-linking is expressed as the weight percent of the cross-linked material. The equipment used to measure the polymer cross-linking percentage includes: 100 mesh (0.0011 cm (0.0045 inch) wire diameter); sus304 stainless steel bag; wire and clips; Miyamoto thermostatic oil bath apparatus; analytical balance; fume hood; gas burner; high temperature oven; antistatic gun; and three 3.5 liter wide-mouth stainless steel containers with lids. The reagents and materials used include tetralin high molecular weight solvent, acetone, and silicone oil. Specifically, the empty wire mesh bag is weighed and the mass is recorded. For each sample, approximately 100 milligrams ± approximately 5 milligrams of sample is weighed and transferred to the wire mesh bag. The mass of the wire mesh bag and the sample (usually foam shreds) is recorded. Attach each bag to a wire and clip of the corresponding size. When the solvent temperature reaches 130°C, immerse the bundle (bag and sample) in the solvent. Shake the sample up and down about 5 or 6 times to release all air bubbles and completely wet the sample. Attach the sample to a stirrer and stir for 3 hours to allow the solvent to dissolve the foam. Then cool the sample in a fume hood. Wash the sample in a container with primary acetone by shaking it up and down about 7 or 8 times. Wash the sample a second time in a second acetone wash. Wash the washed sample again as above in a third container of fresh acetone. Then hang the sample in a fume hood for about 1 to about 5 minutes to allow the acetone to evaporate. Next, dry the sample in a drying oven at 120°C for about 1 hour. Allow to cool for at least about 15 minutes. Weigh the wire mesh bag on an analytical balance and record the mass. The degree of crosslinking is then calculated using the formula 100*(CA) / (BA). where A = mass of empty wire mesh bag, B = mass of wire bag + mass of foam sample before immersion in tetralin, and C = mass of wire bag + mass of sample after dissolution after immersion in tetralin. In general, the preferred value of the degree of crosslinking can be 20 to 75%, more preferably 30 to 60%.
[0171]
[0189] The "Melt Flow Index" (MFI) value of a polymer can be defined and measured according to ASTM D1238 at 230°C for polypropylene and polypropylene-based materials and at 190°C for polyethylene and polyethylene-based materials using a 2.16 kg plunger for 10 minutes. For higher melt flow resins, the test time may be reduced.
[0172]
[0190] This application discloses several numerical ranges in the text and figures. Since the invention can be practiced throughout the disclosed numerical ranges, the disclosed numerical ranges inherently include any range or value within the disclosed numerical ranges, even if an exact range limit is not directly recited in the specification.
[0173]
[0191] The above description is presented to enable one skilled in the art to make and use the invention, and is provided in the context of a particular application and its requirements. Various modifications to the preferred embodiment will be readily apparent to those skilled in the art. Moreover, the general principles defined herein may be applied to other embodiments and applications without departing from the spirit and scope of the invention. Thus, the present invention is not intended to be limited to the embodiments shown, but is to be accorded the widest scope consistent with the principles and features disclosed herein. Finally, the disclosures of all patents and publications referenced in this application are incorporated herein by reference.
Claims
1. 1. A method for forming a multi-layer structure, comprising: a first layer comprising polypropylene or polyethylene and a first chemical blowing agent; co-extruding a second layer on the side of the first layer, the second layer comprising: 5 to 75% by weight of recycled metallized polyolefin material; 25 to 95% by weight of polypropylene, polyethylene, or a combination of polypropylene and polyethylene; and The method further comprising the step of:
2. co-extruding a third layer on a side of the second layer opposite the first layer, the third layer comprising: Polypropylene or polyethylene; and a third chemical blowing agent.
3. 3. The method of claim 2, wherein the first layer and the third layer are substantially free of recycled polyolefin material.
4. 10. The method of claim 1, wherein the recycled metallized polyolefin material is small enough to pass through a 0.95 cm (0.375 inch) standard sieve.
5. 10. The method of claim 1, wherein the recycled metallized polyolefin material has one or more metal layers with a total thickness of 0.003 to 100 μm before being recycled.
6. The method of claim 1, wherein the first layer comprises polypropylene having a melt flow index at 230° C. of 0.1 to 25 grams per 10 minutes.
7. The method of claim 1, wherein the first layer comprises a polyethylene having a melt flow index at 190° C. of 0.1 to 25 grams per 10 minutes.
8. The method of claim 2 , wherein the first and third layers comprise polypropylene and polyethylene.
9. The method of claim 2 , wherein the first layer, the second layer, and the third layer comprise a crosslinker.
10. 3. The method of claim 2, wherein the first, second and third chemical blowing agents comprise azodicarbonamide.
11. 1. A method of forming a multi-layer foam structure, comprising: a first layer comprising polypropylene or polyethylene and a first chemical blowing agent; a second layer on the side of the first layer, 5 to 75% by weight of recycled metallized polyolefin material; 25 to 95% by weight of polypropylene, polyethylene, or a combination of polypropylene and polyethylene; and a second layer comprising a second chemical blowing agent; Co-extrusion, irradiating the coextruded layer with ionizing radiation; and and foaming said irradiated coextruded layer.
12. co-extruding a third layer on a side of the second layer opposite the first layer, the third layer comprising: Polypropylene or polyethylene; and a third chemical blowing agent.
13. 13. The method of claim 12, wherein the first layer and the third layer are substantially free of recycled polyolefin material.
14. 12. The method of claim 11, wherein the ionizing radiation is selected from the group consisting of alpha radiation, beta radiation, gamma radiation, or an electron beam.
15. The method of claim 11 , wherein the coextruded structure is irradiated in up to four separate instances.
16. The method of claim 14, wherein the ionizing radiation is an electron beam having an accelerating voltage of 200 to 1500 kV.
17. The method of claim 16, wherein the absorbed electron dose is from 10 to 500 kGy.
18. The method of claim 11, wherein the ionizing radiation crosslinks the extruded structure to a degree of crosslinking of 20 to 75%.
19. The method of claim 11 , wherein foaming comprises heating the irradiated structure with a molten salt.
20. The multilayer foam structure has a strength of 20 to 250 kg / m 3 The method of claim 11 having a density of
21. 12. The method of claim 11, wherein the multi-layer foam structure has an average closed cell size of 0.05 to 1.0 mm.
22. 12. The method of claim 11, wherein the multi-layer foam structure has a thickness of 0.2 to 50 mm.
23. The method of claim 11 , wherein the average surface roughness of the first layer is less than 80 μm.
24. The method of claim 12 , wherein the first and third layers comprise polypropylene and polyethylene.
25. an extruded first foam layer comprising polypropylene or polyethylene; a coextruded second foam layer on a side of the first foam layer, the second foam layer comprising: 5-75% by weight recycled metallized polyolefin material; and A multi-layer foam structure comprising 25-95% by weight of polypropylene, polyethylene, or a combination of polypropylene and polyethylene.
26. 26. The multi-layer foam structure of claim 25, further comprising a co-extruded third foam layer on the side of the second foam layer opposite the first foam layer, the third foam layer comprising polypropylene or polyethylene.
27. 26. The multi-layer foam structure of claim 25, wherein the first foam layer and the third foam layer are substantially free of recycled polyolefin materials.
28. 27. The multi-layer foam structure of claim 26, wherein the first and third layers comprise polypropylene and polyethylene.
29. 26. The multi-layer foam structure of claim 25, wherein the first layer comprises polypropylene having a melt flow index at 230° C. of 0.1 to 25 grams per 10 minutes.
30. 26. The multi-layer foam structure of claim 25, wherein the first layer comprises a polyethylene having a melt flow index at 190° C. of 0.1 to 25 grams per 10 minutes.
31. Density: 20 to 250 kg / m 3 26. The multilayer foam structure of claim 25, wherein:
32. 26. The multi-layer foam structure of claim 25 having a degree of crosslinking of 20-75%.
33. 26. The multilayer foam structure of claim 25 having an average closed cell size of 0.05 to 1.0 mm.
34. 26. The multilayer foam structure of claim 25 having a thickness of 0.2 to 50 mm.
35. 26. The multi-layer foam structure of claim 25, wherein the average surface roughness of the first foam layer is less than 80 μm.
36. 26. The multilayer foam structure of claim 25, wherein the foam structure is slit, friction sawed, sheared, heat cut, laser cut, plasma cut, water jet cut, die cut, mechanically cut, or manually cut to form an article.
37. a coextruded first foam layer comprising polypropylene or polyethylene; and a coextruded second foam layer on the side of the first foam layer, 5-75% by weight recycled metallized polyolefin material; and a second foam layer comprising 25 to 95% by weight of polypropylene, polyethylene, or a combination of polypropylene and polyethylene; A multi-layer foam structure; a laminate layer on an opposite side of the first foam layer from the second foam layer.
38. 38. The laminate of claim 37, wherein the laminate layer is selected from the group consisting of a film, a fabric, a fiber layer, and leather.
39. 38. The laminate of claim 37, wherein the average surface roughness of the first foam layer is less than 80 μm.
40. 38. The laminate of claim 37, wherein the multi-layer foam structure further comprises a co-extruded third foam layer on an opposite side of the second foam layer from the first foam layer, the third foam layer comprising polypropylene or polyethylene.
41. 41. The laminate of claim 40, wherein the first foam layer and the third foam layer are substantially free of recycled polyolefin material.
42. 41. The laminate of claim 40, further comprising a substrate on a side of the third foam layer opposite the second foam layer, the laminate being thermoformed onto the substrate.
43. 41. The laminate of claim 40, wherein the first and third layers comprise polypropylene and polyethylene.
44. 1. A method for forming a multi-layer structure, comprising: a first layer comprising polypropylene or polyethylene and a first chemical blowing agent; and a second layer on the side of the first layer, the second layer comprising: 5 to 50% by weight of recycled crosslinked polyolefin foam material; 50 to 95% by weight of polypropylene, polyethylene, or a combination of polypropylene and polyethylene; and a second chemical blowing agent.
45. 45. The method of claim 44, wherein the recycled crosslinked polyolefin foam material comprises cryogenically ground polyolefin foam material.
46. co-extruding a third layer on a side of the second layer opposite the first layer, the third layer comprising: Polypropylene or polyethylene; and a third chemical blowing agent.
47. 47. The method of claim 46, wherein the first layer and the third layer are substantially free of recycled polyolefin material.
48. 46. The method of claim 45, wherein the cryogenically ground polyolefin foam material is small enough to pass through a 3.5 U.S. standard mesh.
49. 45. The method of claim 44, wherein the first layer comprises polypropylene having a melt flow index at 230°C of 0.1 to 25 grams per 10 minutes.
50. 45. The method of claim 44, wherein the first layer comprises polyethylene having a melt flow index at 190°C of 0.1 to 25 grams per 10 minutes.
51. 47. The method of claim 46, wherein the first layer, second layer, and third layer comprise a crosslinker.
52. 47. The method of claim 46, wherein the first, second and third chemical blowing agents are azodicarbonamide.
53. 47. The method of claim 46, wherein the first and third layers comprise polypropylene and polyethylene.
54. 1. A method of forming a multi-layer foam structure, comprising: a first layer comprising polypropylene or polyethylene and a first chemical blowing agent; a second layer on the side of the first layer, 5 to 50% by weight of recycled crosslinked polyolefin foam material; 50 to 95% by weight of polypropylene, polyethylene, or a combination of polypropylene and polyethylene; and a second layer comprising a second chemical blowing agent; Co-extrusion, irradiating the coextruded layers with ionizing radiation; and and foaming said irradiated coextruded layer.
55. co-extruding a third layer on a side of the second layer opposite the first layer, the third layer comprising: Polypropylene or polyethylene; and a third chemical blowing agent.
56. 56. The method of claim 55, wherein the first layer and the third layer are substantially free of recycled polyolefin material.
57. 55. The method of claim 54, wherein the recycled crosslinked polyolefin foam material comprises cryogenically ground polyolefin foam material.
58. 55. The method of claim 54, wherein the ionizing radiation is selected from the group consisting of alpha rays, beta rays, gamma rays, or electron beams.
59. 55. The method of claim 54, wherein the coextruded structure is irradiated in up to four separate instances.
60. 59. The method of claim 58, wherein the ionizing radiation is an electron beam having an accelerating voltage of 200 to 1500 kV.
61. 61. The method of claim 60, wherein the absorbed electron dose is from 10 to 500 kGy.
62. 55. The method of claim 54, wherein the ionizing radiation crosslinks the extruded structure to a degree of crosslinking of 20-75%.
63. 55. The method of claim 54, wherein foaming comprises heating the irradiated structure with a molten salt.
64. The multilayer foam structure has a compressive strength of 20 to 250 kg / m 3 The method of claim 54, wherein the density is
65. 55. The method of claim 54, wherein the multilayer foam structure has an average closed cell size of 0.05 to 1.0 mm.
66. 55. The method of claim 54, wherein the multi-layer foam structure has a thickness of 0.2 to 50 mm.
67. 55. The method of claim 54, wherein the average surface roughness of the first layer is less than 80 μm.
68. 56. The method of claim 55, wherein the first and third layers comprise polypropylene and polyethylene.
69. a coextruded first foam layer comprising polypropylene or polyethylene; and a coextruded second foam layer on the side of the first foam layer, the second foam layer comprising: 5 to 50% by weight of recycled crosslinked polyolefin foam material, and A multi-layer foam structure comprising 50-95% by weight of polypropylene, polyethylene, or a combination of polypropylene and polyethylene.
70. 70. The multi-layer foam structure of claim 69, further comprising a co-extruded third foam layer on the side of the second foam layer opposite the first foam layer, the third foam layer comprising polypropylene or polyethylene.
71. 71. The multi-layer foam structure of claim 70, wherein the first foam layer and the third foam layer are substantially free of recycled polyolefin materials.
72. 70. The multi-layer foam structure of claim 69, wherein the recycled crosslinked polyolefin foam material comprises cryogenically ground polyolefin foam material.
73. 70. The multi-layer foam structure of claim 69, wherein the first layer comprises polypropylene having a melt flow index at 230° C. of 0.1 to 25 grams per 10 minutes.
74. 70. The multi-layer foam structure of claim 69, wherein the first layer comprises a polyethylene having a melt flow index at 190° C. of 0.1 to 25 grams per 10 minutes.
75. Density: 20 to 250 kg / m 3 70. The multi-layer foam structure of claim 69, wherein:
76. 70. The multi-layer foam structure of claim 69, having a degree of crosslinking of 20-75%.
77. 70. The multilayer foam structure of claim 69 having an average closed cell size of 0.05 to 1.0 mm.
78. 70. The multi-layer foam structure of claim 69, having a thickness of 0.2 to 50 mm.
79. 70. The multilayer foam structure of claim 69, wherein the first foam layer has an average surface roughness of less than 80 μm.
80. 71. The multi-layer foam structure of claim 70, wherein the first and third layers comprise polypropylene and polyethylene.
81. 70. The multilayer foam structure of claim 69, wherein the foam structure is slit, friction sawed, sheared, heat cut, laser cut, plasma cut, water jet cut, die cut, mechanically cut, or manually cut to form an article.
82. a coextruded first foam layer comprising polypropylene or polyethylene; and a coextruded second foam layer on the side of the first foam layer, 5 to 50% by weight of recycled crosslinked polyolefin foam material, and a second foam layer comprising 50 to 95% by weight of polypropylene, polyethylene, or a combination of polypropylene and polyethylene; A multi-layer foam structure; a laminate layer on an opposite side of the first foam layer from the second foam layer.
83. 83. The laminate of claim 82, wherein the recycled crosslinked polyolefin foam material comprises cryogenically ground polyolefin foam material.
84. 83. The laminate of claim 82, wherein the laminate layer is selected from the group consisting of a film, a fabric, a fiber layer, and leather.
85. 83. The laminate of claim 82, wherein the average surface roughness of the first foam layer is less than 80 μm.
86. 83. The laminate of claim 82, wherein the multi-layer foam structure further comprises a third foam layer on an opposite side of the second foam layer from the first foam layer, the third foam layer comprising polypropylene or polyethylene.
87. 87. The laminate of claim 86, wherein the first foam layer and the third foam layer are substantially free of recycled polyolefin material.
88. 87. The laminate of claim 86, further comprising a substrate on a side of the third foam layer opposite the second foam layer, the laminate being thermoformed onto the substrate.
89. 87. The laminate of claim 86, wherein the first and third layers comprise polypropylene and polyethylene.
90. 1. A method for forming a multi-layer structure, comprising: a foam layer comprising polypropylene or polyethylene and a chemical blowing agent; a film layer on a side of the foam layer, A film layer containing polypropylene or polyethylene. The method comprises co-extruding.
91. 91. The method of claim 90, wherein the foam layer comprises polypropylene having a melt flow index of 0.1 to 25 grams per 10 minutes at 230°C.
92. 91. The method of claim 90, wherein the foam layer comprises polyethylene having a melt flow index of 0.1 to 25 grams per 10 minutes at 190°C.
93. 91. The method of claim 90, wherein the foam layer comprises a crosslinking agent.
94. 91. The method of claim 90, wherein the chemical blowing agent comprises azodicarbonamide.
95. 91. The method of claim 90, wherein the foam layer comprises polypropylene and polyethylene.
96. 1. A method of forming a multi-layer foam structure, comprising: a foam layer comprising polypropylene or polyethylene and a chemical blowing agent; a film layer on a side of the foam layer, A film layer containing polypropylene or polyethylene. Co-extrusion, irradiating the coextruded layer with ionizing radiation; and foaming the irradiated coextruded layer. The method includes:
97. 97. The method of claim 96, wherein the ionizing radiation is selected from the group consisting of alpha rays, beta rays, gamma rays, or electron beams.
98. 97. The method of claim 96, wherein the coextruded structure is irradiated in up to four instalments.
99. 98. The method of claim 97, wherein the ionizing radiation is an electron beam having an accelerating voltage of 200 to 1500 kV.
100. 100. The method of claim 99, wherein the absorbed electron dose is from 10 to 500 kGy.
101. 97. The method of claim 96, wherein the ionizing radiation crosslinks the extruded structure to a degree of crosslinking of 20-75%.
102. 97. The method of claim 96, wherein foaming comprises heating the irradiated structure with a molten salt.
103. The multilayer foam structure has a compressive strength of 20 to 250 kg / m 3 97. The method of claim 96, having a density of
104. 97. The method of claim 96, wherein the multilayer foam structure has an average closed cell size of 0.05 to 1.0 mm.
105. 97. The method of claim 96, wherein the multi-layer foam structure has a thickness of 0.2 to 50 mm.
106. 97. The method of claim 96, wherein the foam layer has an average surface roughness of less than 80 μm.
107. 97. The method of claim 96, wherein the foam layer comprises polypropylene and polyethylene.
108. 1. A method for forming a multi-layer structure, comprising: a first foam layer comprising polypropylene or polyethylene and a first chemical blowing agent; a second foam layer on a side of the first foam layer, Polypropylene or polyethylene, and a second foam layer comprising a second chemical blowing agent; The method comprises co-extruding.
109. 109. The method of claim 108, wherein the first and second layers comprise polypropylene having a melt flow index at 230° C. of 0.1 to 25 grams per 10 minutes.
110. 109. The method of claim 108, wherein the first and second layers comprise polyethylene having a melt flow index of 0.1 to 25 grams per 10 minutes at 190°C.
111. 109. The method of claim 108, wherein the first and second layers comprise a crosslinking agent.
112. 109. The method of claim 108, wherein the first and second chemical blowing agents comprise azodicarbonamide.
113. 109. The method of claim 108, wherein the first and second layers comprise polypropylene and polyethylene.
114. 1. A method of forming a multi-layer foam structure, comprising: a first foam layer comprising polypropylene or polyethylene and a first chemical blowing agent; a second foam layer on a side of the first foam layer, Polypropylene or polyethylene, and a second foam layer comprising a second chemical blowing agent; Co-extrusion, irradiating the coextruded layers with ionizing radiation; and foaming the irradiated coextruded layer; The method includes:
115. 115. The method of claim 114, wherein the ionizing radiation is selected from the group consisting of alpha rays, beta rays, gamma rays, or electron beams.
116. 115. The method of claim 114, wherein the coextruded structure is irradiated in up to four instalments.
117. 116. The method of claim 115, wherein the ionizing radiation is an electron beam having an accelerating voltage of 200 to 1500 kV.
118. 118. The method of claim 117, wherein the absorbed electron dose is from 10 to 500 kGy.
119. 115. The method of claim 114, wherein the ionizing radiation crosslinks the extruded structure to a degree of crosslinking of 20-75%.
120. 115. The method of claim 114, wherein foaming comprises heating the irradiated structure with molten salt.
121. The multilayer foam structure has a compressive strength of 20 to 250 kg / m 3 The method of claim 114, having a density of
122. 115. The method of claim 114, wherein the multilayer foam structure has an average closed cell size of 0.05 to 1.0 mm.
123. 115. The method of claim 114, wherein the multi-layer foam structure has a thickness of 0.2 to 50 mm.
124. 115. The method of claim 114, wherein the average surface roughness of the first foam layer is less than 80 μm.
125. 115. The method of claim 114, wherein the first and second layers comprise polypropylene and polyethylene.